Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

The application of RPA-PfAgo technology combined with multidimensional data analysis in the rapid detection of the MTHFR A1298C polymorphism - Yaqun Liu; Lianghui Chen; Xuanyi Zheng; Peikui Yang; Jinkun Han; Jiayi Huang; Yanling Shen; Xiaotong Cai; Miaofen Fang; Yicun Chen; Chengsong Xie; Min Lin; et al. (Functional & Integrative Genomics, 2026)

DBF4B promotes hepatocellular carcinoma progression by regulating CCNA2 and PSMD11 expression - Bing Dong; Pengju Xi; Guangxin Yang; Zhiqi Jiao; Shijie Xu; Lin Han; Zhenming Gao (Molecular Biology Reports, 2026)

Monsoon and Westerlies drive particle size sorting of microplastics in the riparian zone of the Tibetan Plateau interior - Qinghui Zeng; He Gao; Yang Zhou; Suxing Fu; Huixin Zeng; Chaowei Zhou; Zhaofang Han; Jian Su; Kexin Ma; Junting Li; Lin Zhou; Haiping Liu (Water Research, 2026)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

Effects of sustained eccentric loading on concrete-encased concrete-filled steel tubular (CFST) columns - Zhi-Cheng Yang; Di Fan; Guan-Yuan Zhao; Li Zhu; Lin-Hai Han; Chen-Yu Zhang (Engineering Structures, 2026)

Flexural performance and calculations of concrete-encased square concrete-filled steel tubular (CFST) hybrid structures - Dan-Yang Ma; Jie Gong; Lin-Hai Han; Long-Hui Du (Engineering Structures, 2026)

Structural assessment of post-impact concrete-filled steel tubular (CFST) members based on vibration tests and Bayesian model updating - Shang-Jun Chen; Chuan-Chuan Hou; Lin-Hai Han; Hua Yang (Engineering Structures, 2026)

Structural engineering of Cu/SiO2 catalysts via controlled hydrothermal treatment: Unveiling the role of silanol evolution and Cu dispersion for enhanced DMO hydrogenation to ethylene glycol - Jinxia Yang; Xiaoqian Lin; Zhenhong Han; Xin Zhang; Yuangen Yao (Chemical Engineering Journal, 2026)

General applicability for developing interfacial regulation materials: An artificial-intelligence-driven approach based on non-covalent interactions - Changqing He; Yang Xue; Huimin Zhou; Xincheng Zhang; Xueqian Liu; Lin He; Hong Sui; Zhenghe Xu; You Han (Chemical Engineering Journal, 2026)

Genomic and biosynthetic landscape of high-temperature Daqu microbiome - Mingyue Cheng; Xing Qin; Ying Han; Fanggen Tan; Menglin She; Xue Zhu; Lin Yuan; Mengjing Teng; Xiyang Ou; Sha Luo; Ping Xiang; Liangqiang Chen; et al. (Bioresource Technology, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Light parameters and iron ions regulate mass-independent fractionation via modulating degradation pathways of methylmercury - Kun Zhang; Lin Yang; Deming Han; Cailing Xiao; Yongguang Yin; Ligang Hu; Yong Liang; Jianbo Shi; Guibin Jiang (Water Research, 2026)

Temporal sulfur redox reprogramming enables control-oriented intensification of sulfur-based autotrophic denitrification - Kun Zheng; Han-Bing Xiao; Yi-Lu Sun; Zhou-Yang Li; Jing-Zhe Zhang; Han-Lin Wang; Ai-Jie Wang; Xue-Ning Zhang (Water Research, 2026)

Nitrite reductases: From structure–function relationships to biocatalytic nitrite depletion and detection - Lin Yuan; Fang Wang; Han Zhang; Shu-Yu Ding; Zhong-Hua Yang (Trends in Food Science & Technology, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Selective iron removal from Fe-PGMs alloys for platinum group metals concentration: Dissolution behavior of PGMs and ultrasound-assisted leaching - Han Yang; Yong Li; Xilong Wu; Ruiling Yuan; Chao Wang; Shengnan Lin; Jibiao Han; Kuo Liu (Journal of Environmental Chemical Engineering, 2026)

N-3 PUFA deposition and esterification patterns drive aroma profile remodeling in the longissimus dorsi of pigs fed flaxseed oil - Yingsen Liu; Longzhu Zhou; Luxi Lin; Shijie Wang; Yiyu Yin; Haoyang Han; Huihui Tian; Miaomiao Dong; Pingyang Li; Youyou Yang; Xiaohui Feng; Weihai Xing; et al. (Food Chemistry, 2026)

Preparation of plant-based meat analogues by soft matter method: Effects of NaCl concentrations and addition order - Jing-Wen Zhang; Qin Yang; Hui-Lin Li; Qing-Xuan Liu; Han-Qing Chen (Food Hydrocolloids, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

A tetrahedral framework DNA-metformin nano-firefighter for quenching adipose chronic inflammation: Reprogramming macrophages to restore metabolic homeostasis in obesity - Zhuo Chen; Jiaqi Li; Alimire Alifu; Fenglin Jiang; Wenjing Tang; Zaowei Yang; Yuhao Liu; Bo Tian; Xi Chen; Yu Chen; Qi Han; Yunfeng Lin (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Enhanced phenanthrene degradation in microalgae-bacteria systems: Mechanistic roles of exogenous and indigenous degraders - Mengying Wang; Han Wang; Xuetao Liang; Jingran Li; Chen Wang; Longyan Cui; Shuo Yang; Jiaxuan Lin; Qi Yang; Zhilin Yang (Bioresource Technology, 2026)

TEC2Ne: a physics-informed deep learning framework for reconstructing ionospheric electron density profiles from global TEC maps - Chenghao Li; Hanxian Fang; Chao Xiao; Die Duan; Yang Lin; Hongtao Huang; Ganming Ren; Han Wu; Chuyue Zhou; Haiyang Zheng; Xuhui Shen; Xiaoqun Cao (GPS Solutions, 2026)

Development of a frost-specific module and its integration into a process-based model for winter wheat frost damage simulation - Yuanda Zhang; Peijuan Wang; Yuping Ma; Lin Cheng; Yang Li; Dianchen Han; Dingrong Wu; Shuxian Liu; Jianping Guo (Agricultural and Forest Meteorology, 2026)

Mechanisms of Dissolved Organic Matter Migration in Coal Mining Subsidence Areas - Jing Xu; Liangmin Gao; Jinxiang Yang; Jieyu Xia; Han Song; Yanjun Liu; Kai Zhang; Lin Wu; Xin Shu (Mine Water and the Environment, 2026)

The impact of the blue bay initiative on the coastal tourism economy in China: an intensity difference-in-differences analysis - Yuhu Cui; Hanxiao Xu; Guosheng Han; Hong Ching Goh; Lin Yang (Environment, Development and Sustainability, 2026)

Human-relevant co-exposure to 6:2 Cl-PFESA and PFHxS impairs sperm motility and blood-testis barrier integrity in male mice: Evaluation of combined effects - Lan Shi; Tianrui Gao; Zhipeng Zhu; Fan Yang; Bing Han; Jia Lv; Lin Tao; Yang Gao; Rong Hua; Huan Wu; Yichao Huang; Xiaojin He (Journal of Hazardous Materials, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Natural occurrence and dietary risk assessment of Alternaria toxins in wheat flour and its products in Shanghai, China - Jinhui Xue; Zhiqi Zhang; Dongxia Nie; Kai Fan; Jiajia Meng; Meng Cheng; Xialin Lin; Xianli Yang; Zhihui Zhao; Zheng Han (Food Research International, 2026)

Tailored high internal phase emulsion-filled/emulsion particulate gels based on gelatin/agar by cold gelation: stability, rheological behaviors, and delivery properties - Fengrui Zhang; Zhishuang Ma; Junqi Han; Xingbin Yang; Dehui Lin (Food Hydrocolloids, 2026)

Behaviour of concrete-encased CFST hybrid member subjected to long-term bending moments - Chen-Yu Zhang; Guan-Yuan Zhao; Lin-Hai Han; Zhi-Cheng Yang (Engineering Structures, 2026)

Benchmarking backbone neural networks for HVAC fault diagnosis and regression: Insights into spatiotemporal, graph, and attention-based architectures - Zhe Sun; Peng Yang; Ling Shi; Qiwei Yao; Lin Li; Han Xiao; Xiangwei Zheng; Xi Shen (Energy and Buildings, 2026)

Multichannel epicardial bioelectronics via a stretchable, wet-adhesive, antibacterial hydrogel with highly conformable Interface - Si Shen; Xingyun Fan; Weibin Liang; Chenghua Xie; Nian Zhang; Pengqi Wang; Rurong Lin; Jie Zhang; Yanni Han; Chongyin Qiu; Shiqi Guo; Jingxing Dai; et al. (Chemical Engineering Journal, 2026)

An intelligent nanosystem for disrupting the neuro-immune-oncology axis to unleash anti-tumor “immune storm” - Yuanhang Han; Yunxiang Ding; Yuyang Wang; Zhiqiang Yang; Xiaoxiao Liang; Xin Wang; Yushen Lu; Ruimin Wang; Zhenyi Chen; Yifan Hu; Lin Cai; Jianbin Xu; et al. (Chemical Engineering Journal, 2026)

A fountain pen strategy for writing flexible electronics with low-temperature chemical reactive silver ink - Jiayang Lin; Yi Zhao; Jie You; Fangzu Yang; Ren Hu; Jian-Jia Su; Yuanfei Wu; Lianhuan Han; Dongping Zhan (Chemical Engineering Journal, 2026)

Microplastic type influences soil phosphorus availability independently of long-term cropping systems and fertilization regimes - Xuechen Yang; Lin Han; Raúl Ochoa-Hueso; Jingjie Dou; Peng He; Yakov Kuzyakov; Wenzheng Song; Xiaowei Wei; Yueyu Sui; Xiangxiang Hao; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2026)

LC-MS-based metabolomics reveals the In Vivo effects of cognitive formula 1 in rats with Aβ-induced Alzheimer’s disease - Di Wu; Yanling Lin; Wenjun Guo; Zengling Wang; Yan Chang; Jing Yan; Daqing Han; Ke Xiang; Zhen Yang (Experimental Brain Research, 2026)

Characterization of a novel Era-homolog (AtERG1) in Arabidopsis that is essential for chloroplast development - Yi Lin; Shuangyuan Jia; Chenchen Zhang; Shanshan Chen; Han Xiang; Jiaqi Chen; Ying Yang; Jiawei Chen; Ming Li; Jinwen Liu (Journal of Plant Biochemistry and Biotechnology, 2026)

THBS2: the key hub linking breast cancer stroma, immunity, and therapeutic response - Xi Wan; Xinchen Zhao; Yao Lin; Shujie Yang; Han Dai; Yi Li; Xiaoshan Wang (Clinical & Experimental Metastasis, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Robust source tracing for solid waste via machine learning-enabled mineralogical fingerprinting - Le Lin; Changhai Ren; Shen Qu; Yang Xiao; Yin Li; Xueming Liu; Han Wang; Zhang Lin (Resources, Conservation and Recycling, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

New insight into mercury sources and trophic transfer in the Bohai Sea food web using carbon, nitrogen, and mercury stable isotopes - Xiaowei Qiao; Shuangxu Zhou; Lin Yang; Hua Guo; Tao Yang; Wenjing Li; Zhuo Ma; Deming Han; Jianbo Shi; Guibin Jiang (Journal of Hazardous Materials, 2026)

MRI-guided nano-prodrug with self-detoxifying bioclearance for precision detection and therapy of cancer metastases - Wenyi Zhang; Dengyi Duan; Jing Peng; Lin Chen; Kangkang Liu; Yiming Li; Jianmin Li; Gang Han; Yang Zhao (Chemical Engineering Journal, 2026)

Denitrogenation of aqueous organic nitrogen by vacuum ultraviolet in tandem with chlorine - Baiyang Chen; Hao-Lin Yang; Longjie Cheng; Yuheng Chen; Xiao Li; Qiaoxia Han (Chemical Engineering Journal, 2026)

A subcellular spatial profiling platform for expanding the drug toxicity window - Liu Yang; Qingjie Bai; Shuyuan Guo; Luyao Hu; Chenghao Bi; Litao Shao; Zihao Lin; Kairui Cui; Shenshen Yang; Jinxia Wei; Liwei Shao; Liwen Han; et al. (Chemical Engineering Journal, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Nighttime growth in the green tide alga Ulva prolifera: metabolic basis and ecological implications - Han Xu; Mingzi Lin; Jiaying Bian; Dongyi Yang; Jianan Jiang; Shenyuan Liang; Hao Zhang; Wenrong Zhu; Nianjun Xu; Yahe Li (Journal of Applied Phycology, 2026)

FAL1 facilitates cisplatin resistance of lung adenocarcinoma via BMI1/BIM-mediated apoptosis–autophagy interaction - Teng Ma; Yang Xia; Yijiang Chen; Han Lin; Chunfeng Pan (Molecular and Cellular Biochemistry, 2026)

Neural network approach for predicting outcomes of external cephalic version for breech presentation: a retrospective cohort study - Yuting Xiang; Wenjian Yang; Haote Han; Haixia Lin; Wanhua Wu; Suran Huang; Hao Wang; Ning Hu; Zhongjun Li (Journal of Zhejiang University-SCIENCE B, 2026)

Critical assessment of synthetic microbial community strategies in vinegar brewing: from design paradigms to industrialization bottlenecks - Shiyuan Lin; Yongjian Yu; Yuanyuan Zhu; Ke Wang; Zhen Yu; Yuqin Wang; Dong Han; Xuezhi Wu; Nan Zhang; Shuaiwei Dou; Yunsong Yang (Critical Reviews in Food Science and Nutrition, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Experimental behaviour of concrete-encased square concrete-filled steel tubular (CFST) hybrid structure subjected to axial compression - Dan-Yang Ma; Long-Hui Du; Lin-Hai Han (Engineering Structures, 2026)

Layered double hydroxide/Cu-luteolin nanoparticle-loaded hydrogel coating: Promoting healing of infected bone defects - Zitong Tian; Jian Yin; Yakun Mao; Hao Yang; Pengde Han; Lili Song; He Lin; Lei Xie; Xiao Huang; Kongpeng Lv; Yong Huang (Chemical Engineering Journal, 2026)

A low-power and visualized varicose vein ablation surgery based on interventional optical fiber therapeutic probe - Fangzhou Jin; Yinsheng Lin; Yading Luo; Jian Han; Xu Yue; Wenwei Chen; Yongkang Zhang; Shanshan Guo; Xiaobing Niu; Jun Guo; Bai-Ou Guan; Chengzhi Li; et al. (Chemical Engineering Journal, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Bimetallic MOF/3D exosomes-loaded gelatin-dialdehyde starch hydrogel coating: Multimodal regulation of the bone-implant interface - Hui Su; Jian Yin; Jialu Wei; Hao Yang; Pengde Han; Zhangping Wang; He Lin; Lei Xie; Xiao Huang; Jinping Lan; Yong Huang (Chemical Engineering Journal, 2026)

Metabolic process and mechanistic model of white-rot fungi degrading plastic films by solid-state fermentation - Zhi Guo; Lin Yao; Xingpan Guo; Lishou Han; Yuanyuan Zha; Xinlei Ling; Fan Yang (Bioresource Technology, 2026)

Field Study of Immobilization Materials and Foliar Inhibitors: Balancing Rice Yield, Safety, and Economy in Cd-As Contaminated Soils - Junchun Li; Longyong Lin; Yirong Deng; Sheng Cheng; Xiao Yang; Xiulan Yan; Qian Yao; Cunliang Han (Water, Air, & Soil Pollution, 2026)

Multidimensional chemoprofiling of hybrid and wild Broussonetia papyrifera : sustainable utilization analysis of wild resource substitutes - Yue Ren; Ziye Cheng; Chunmei Yang; Long Han; Xianjun He; Yuqi Liu; Lin Ma; Chuhan Wang; Ziyi Shan; Wen Qin; Xiaofan Yuan (Natural Product Research, 2026)

Macro-micro mechanical properties and modified damage constitutive model of marine soil after cement reinforcement - Xiao-Hu Zhang; Jian-Min Yang; Han-Lin Wang; Cheng-Shuang Yin; Liu-Mei Wei; Wen-Han Yu; Kamchibek Kozhogulov (Marine Georesources & Geotechnology, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Physics-informed deep learning for hillslope subsurface flow prediction: integrating soil moisture deficit constraints - Xiaole Han; Man Gao; Jintao Liu; Hai Yang; Haoming Lin; Xuhui Shen (Journal of Hydrology, 2026)

Mechanistic insights into UV/H2O2-aged polystyrene enable an optimized protocol for fungal biodegradation - Zhi Guo; Yuanyuan Zha; Xingpan Guo; Xinlei Ling; Lin Yao; Lishou Han; Fan Yang (Journal of Environmental Chemical Engineering, 2026)

In-situ construction of a polydopamine@ZIF-8 functional layer on PES ultrafiltration membranes for high-flux, antifouling dye/salt separation - Deyi Han; Lin Ding; Shujuan Yang; Yong Zhang; Haichuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Overlooked spectral matching-Enabled sulfoxide wastewater valorization and in situ pollutant elimination - Lingzhi Shen; Yue Yang; Yixun Zheng; Mengyang Niu; Zhiqing Lin; Zihong Xu; Yongpeng Zhang; Shan Yao; Yanli Wang; Kun Zhao; Zhenjun Xiao; Zili Lin; et al. (Journal of Cleaner Production, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

A dual-functional fluorescent sensor based on a single soybean-derived carbon dots for discrimination and quantification of tetracyclines in food - Xin Lin; Jiaqi Wang; Meiqi Xia; Shuang Li; Yixin Xu; Jingyi Sun; Han Leng; Tianqun Song; Yanzhi Xing; Mei Yang (Food Chemistry, 2026)

Formation and evolution of sandy deserts in China: A review - Xin Wang; Ziying Yu; Han Hu; Chongwen Luo; Wenjing Yang; Jiayi Lin; Yu Cao; Zaijun Li; Fei Wang; Baofeng Li; Shengqian Chen; Huayu Lu; et al. (Earth-Science Reviews, 2026)

ErbB4 in the Dorsolateral Prefrontal Cortex is Required for Sensory Gating and Working Memory in Monkey - Minzhe Yang; Yingying Han; Hongfei Zhang; Chaolin Ma; Lin Mei; Baoming Li (Neuroscience Bulletin, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Reinforced stepwise dissociation of water molecules via U 5f-O 2p-Ti 3d gradient orbital coupling for photoelectrochemical water splitting - Xiaochuan Deng; Tong Liu; Xudong Wu; Qijue Lin; Hanlin Liu; Han Yang; Xun Yang; Maoyin Wang; Kaiguo Chen; Jiayu Dai; Tao Chen; Wenkun Zhu (Science Bulletin, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Effects of prenatal exposure to hexafluoropropylene oxide dimer acid on rat and offspring mammary gland development and associated hormone levels - Lu Liu; Wendong Liu; Libing Wang; Wenjing Zhu; Dongmei Jia; Yuxin Lin; Zhugen Yang; Kui Che; Wenchao Han (Chemico-Biological Interactions, 2026)

Rapid enrichment of ternary carbon-fixing microbial consortia from anaerobic sludge via pressurized pre-autotrophic strategy for scalable microbial electrosynthesis - Lin-xiao Li; Tian-tian Yang; Yue Yuan; Yi-lian Han; Qian Zhao; Wen-han Wang; Yue Sun; Xiao-xin Cao; Xin-lei Jiang; Tian Li; Xin Wang (Bioresource Technology, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Effect of ivarmacitinib on swelling and tenderness in small and large joints and imaging changes in patients with moderate-to-severe RA: a post hoc analysis of a phase III clinical trial - Yuxiang Han; Meng Ding; Shaoxin Cui; Yu Tian; Yushu Yang; Xuying Liu; Lin Yang; Xiaoping Wang; Hongtao Jin; Huifang Guo; Haixue Dai; Shanshan Yin; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Microneedle-mediated delivery of hydroxypropyl-β-cyclodextrin-encapsulated Angelica sinensis (Danggui) essential oil for acne treatment: efficacy and mechanisms - Xiaoli Liu; Xiaojuan Li; Weijun He; Xiaoyu Han; Ting Xiao; Shiqi Guo; Yujie Jia; Liqun Lin; Ming Yang; Li Wang; Yuehong Xu (Drug Delivery and Translational Research, 2026)

17β-Estradiol alleviates cognitive deficits by modulating fear memory reconsolidation in a PTSD rat model - Han Wang; Han Lin; Zilong Zhong; Baoying Jiang; Siyi Li; Jiahao Tang; Xiaoping Zhou; Guohui Zhu; Yang Liu; Wenhao Han; Jinhua Dou; Lin Sun (Psychopharmacology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Identification and algicidal mechanism of extracellular polysaccharides from Sulfitobacter pseudonitzschiae H46: A novel biocontrol agent for Chattonella marina bloom - Jiaxuan He; Lin Yang; Xin Yin; Jiahui Zhao; Yadan Deng; Jinfeng Ding; Shuai Wang; Bin Han; Li Zheng (Harmful Algae, 2026)

Active faulting and crustal deformation along the East Sunda-Banda Arc: Implications for Regional Geohazards - Xiaodong Yang; Xiwu Luan; Liangyu Zhu; Xinze Han; Zhiwen Zhang; Zhiyuan Zhou; Jian Lin; Liming Wang (Global and Planetary Change, 2026)

Pathway toward carbon neutrality of cement industry: A comprehensive analysis based on microdata - Mengling Zhang; Baokun Li; Hairui Yang; Man Zhang; Dongfang Li; Xing Zhu; Runsheng Lin; Yongkang Han; Aoyang Zhang (Fuel, 2026)

Corrigendum to “Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration”. [229 (2026) 118495/FRIN 118495] - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Biomimetic fabrication of cultured meat using 3D-printed microgrooved and meshed scaffolds with alternating muscle and adipose layers - Chi-Han Li; Chih-Ying Chi; Feng-Huei Lin; Chia-Ting Chang; I-Hsuan Yang (Food Hydrocolloids, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

CoFe Prussian blue analogue photothermal self-healing coating for resistance to corrosion, UV degradation and mold - Yang Han; Qiang Sun; Lin Cao; Han Li; Lankun Liu; Zihan Li; Wei Wang (Chemical Engineering Journal, 2026)

Eco-Friendly Dust Control Strategies: A Critical Review of Chemical Suppressants for Sustainable Environmental Management - Nini Wang; Zhihui Huang; Lin Yang; Tingting Han; Nan Wang; Xiangpeng Meng; Wei Zhang (Water, Air, & Soil Pollution, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Genetic Diversity of Spodoptera litura in China Based on Mitochondrial DNA Analysis - Yu-Lin Li; Jian-Kun Long; Zhi-Ming Chang; Han-Cheng Wang; Jian-Yu Meng; Lin Yang; Jun-Yi Gao; Xiang-Sheng Chen (Phytoparasitica, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Potential application prospects of white-rot fungi in composting degradation for plastic film waste - Zhi Guo; Lin Yao; Xingpan Guo; Yuanyuan Zha; Lishou Han; Xinlei Ling; Fan Yang (Journal of Environmental Sciences, 2026)

Does rural households’ participation in watershed eco-compensation policies help reduce their livelihood vulnerability? Findings from the Xin’an river basin - Yisheng Ren; Han Han; Lin Lu; Hao Cheng; Cheng Yang (Journal for Nature Conservation, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Unraveling the aromatic essence of baked green tea using sensomics: insights from three representative cultivars - Yan Zhao; Chen-Yang Shao; Han Yan; Yue Zhang; Qun-Hua Peng; Zhi Lin; Xiao-Ting Zhai; Hai-Peng Lv; Yin Zhu (Food Chemistry, 2026)

Interactive effects of irrigation and planting density on photosynthetic performance and yield of winter wheat - Muhammad Fraz Ali; Liijuan Ma; Wanrui Han; Yang Zhou; Shengnan Wang; Xiang Lin; Dong Wang (Field Crops Research, 2026)

Magnetic properties driving nitrogen removal improvement in magnetite-enhanced activated sludge: Mechanistic insights and process validation - Jun Shi; Luo-Kai Li; Li-Han Lin; Duo-Kun Li; Jian Lu; Sali Mustafa Saleh; Tian-Yang Zhang; Huan He; Zheng-Yu Dong; Qian Xiao; Bin Xu; Chao Zeng (Environmental Research, 2026)

Hydroxyl-functionalized electrolyte additives for stable low-temperature zinc-ion battery operation - Zhenzhen Kong; Xiyan Wei; Yongbiao Mu; Jinpeng Guan; Zetao Chen; Lin Yang; Liying Wang; Meisheng Han; Lin Zeng (Chemical Engineering Journal, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Fuel–oxidizer integrated ionic liquid for electrically controlled solid propellants based on hydroxylammonium nitrate - Qiyang Wang; Haoyang Lu; Haoqi Guo; Boya Zhang; Ziyang Han; Jian Zhang; Debin Xia; Ping Wang; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2026)

Spatiotemporal variations in indoor thermal environments and dynamic comfort of passengers in airport terminals during winter - Yuxin Yang; Juan Yu; Deyin Zhang; Hao Tang; Wenzhong Jiang; Libin Han; Junmin Li; Borong Lin; Yu Dong (Building and Environment, 2026)

Impacts of structurally distinct starches on growth, short-chain fatty acid production, hepatic lipid metabolic homeostasis, and inflammatory response in largemouth bass (Micropterus salmoides) - Han Huang; Xin Liu; Hao Sun; Yang Xiao; Yuanfa He; Yongjun Chen; Shimei Lin (Animal Feed Science and Technology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

SUMO1 promotes malignancy and chemoresistance in colorectal cancer: Clinical and functional evidence - Anran Xu; Tianyuan Tan; Lin Yuan; Wei Yan; Yang Han; Su Lu (Tissue and Cell, 2026)

Microplastics enhance soil nitrogen availability by stimulating nitrogen-acquiring enzyme activity over three decades-long fertilization regimes - Lin Han; Jingjie Dou; Kai Zhu; Lu-Jun Li; Peng He; Xiaowei Wei; Xiaojing Hu; Yueyu Sui; Xiangxiang Hao; Xuechen Yang (Soil and Tillage Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Methyl group donor‑resolved isotopic diagnostics reveal mechanistic diversity in UV‑driven methylation of Hg(II) - Lin Yang; Kun Zhang; Maojun Yu; Shiyu Li; Deming Han; Ben Yu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Journal of Hazardous Materials, 2026)

Optimizing collaborative management decision-making in large watersheds through seasonal dynamic water quality diagnosis - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Cleaner Production, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Agglomeration of coal gangue particles in an ultra-supercritical CFB boiler: microstructure, thermodynamic modeling, mechanisms and prevention methods - Xiuting Yang; Junjie Li; Seokgi Ahn; Yongkang Han; Lin Pu; Chung-Hwan Jeon; Hua Wang; Xing Zhu; Tao Zhu; Dongfang Li (Fuel, 2026)

Impact of algal blooms on phosphorus migration: Insights from laboratory and field cultivation enrichment experiments in the yangtze river estuary - Yu-Yuan Wang; Zhi-Li Guo; Han-Lin Jiang; Yuan-Zhe Ni; Li-Min Zhou; Gui-Peng Yang; Xiao-Yan Cao (Estuarine, Coastal and Shelf Science, 2026)

Electric field superposition for efficient implantable ultrasound energy harvesting - Aokai Yang; Chaoran Tan; Yuyang Lin; Haoying Han; Renfei Wei; Yan Wang; Kang Chen; Shizhe Lin; Liang Huang; Jun Zhou (Chemical Engineering Journal, 2026)

Combustion acceleration in Al/CuO nanothermite films via gap-induced particle-advection mechanism - Xiaoxia Ma; Changcheng Bao; Lin Shi; Junzhe Xu; Wei Liu; Jimin Han; Li Yang (Chemical Engineering Journal, 2026)

Shen-Ling-Bai-Zhu-San alleviates ulcerative colitis by enhancing mitophagy via the Nrf2/PINK1/Parkin pathway - Huan Wang; Jian Han; Lin Li; Yan Li; Jun Yang; Wangzhong Qiu; Liuhua Yao; Jianjun Zhou (Journal of Molecular Histology, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

Monocyte-mediated mechanisms in idiopathic pulmonary fibrosis: opportunities for early intervention - Zhiguo Mao; Ying Liu; Chengfu Han; Xingyi Yang; Xiangke Lin; Shuo Tian; Mingsan Miao (Apoptosis, 2026)

Implementation of a Deep Learning Ensemble Framework Based on Bidirectional Message Queues - Xin-Jian Wei; Wu-Yang Yang; Xin Xu; Hai-Shan Li; Nan Wang; Wei-Sheng Wang; Han-Wei Lin; Chen Wang (Applied Geophysics, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Coupled polyphosphate storage and DOP mobilization along estuarine gradients in the Pearl River Estuary - Xian-Yang Zhang; Feng-Xian Han; Jian-Ting Li; Jia-Xue Wu; Song-Hui Lu; Lin-Jian Ou (Marine Pollution Bulletin, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Insight into the profiles and sources of free amino acids (FAAs) and combined amino acids (CAAs) in PM2.5 over Xi'an, China - Xiaoyan Hu; Liu Yang; Hongai Zhang; Lin Han; Hongmei Xu; Zhenxing Shen (Science of The Total Environment, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Comparison of metabolomic and transcriptomic analyses of Ganping mandarin fruit following on tree storage and postharvest low temperature storage - Xinyu Huang; Luoao Lin; John B. Golding; Penta Pristijono; Su Guo; Youjian Yu; Gang Chen; Dongdao Han; Huqing Yang; Ruihua Bai; Yongxin Li (Postharvest Biology and Technology, 2026)

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Acicular berthierine-chamosite in coal and lung cancer tissues of Xuan Wei, China - Zheshen Han; Hongli Lin; Renyue Ji; Lijun Liu; Pei Zhang; Chao Jiang; Shijie Zhu; Jialin Xu; Zhenghong Yang; Yunchao Huang; Toshihiro Kogure; Fang Guo; et al. (Journal of Hazardous Materials, 2026)

Nonlinear microbial nutrient limitation responses to biodegradable vs. conventional microplastics under long-term agricultural management - Jingjie Dou; Lin Han; Xiaojing Hu; Lu-Jun Li; Peng He; Junhui Wang; Xiangxiang Hao; Yueyu Sui; Wei Sun; Xuechen Yang (Journal of Hazardous Materials, 2026)

Distinct links between climate warming, mariculture activities, and coastal benthic ecosystem change - Yong Xu; Jixing Sui; Lin Ma; Jinbao Wang; Qi Kou; Zhibin Gan; Lin Gong; Mei Yang; Qingxi Han; Xinzheng Li; Dong Dong (Journal of Environmental Management, 2026)

Dominant governing mechanisms of deformation-seepage and dynamic evolution model of permeability in gas-containing coal under coupled stress-pore pressure - Chongzhi Wang; Bin Zhou; Shugang Li; Haifei Lin; Haiqing Shuang; Dongming Zhang; Shoujian Peng; Liang Cheng; Han Yang (Fuel, 2026)

A novel aqueous synthesis of anion exchange membranes for fuel cells - Xia Liu; Zhongshan Feng; Cuiwen Deng; Quan Yang; Minhao Wang; Xinjie Zhang; Yi Hu; Yufan Zheng; Juan Zeng; Bencai Lin; Juanjuan Han (Fuel, 2026)

Optimization of bacterial nanocellulose synthesis using surfactants for immobilization of Saccharomyces cerevisiae to enhance resistance to lignocellulose-derived inhibitor - Yetong Feng; Dingkang Wei; Shuai Han; Peihong Chen; Jie Liu; Tao Chen; Yiran Yan; Yang Bai; Linxu Chen; Jianqun Lin; Jianqiang Lin; Zixiang Xu; et al. (Bioresource Technology, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Identification of Axonal Regeneration-Related Genes and a Potential Analgesic Drug for Neuropathic Pain - Yang Liu; Yongxue Zhang; Shikang Hao; Yabin Shi; Xiaoyue Chen; Zhibin Ye; Guona Zheng; Lin Kang; Han Hao (Molecular Neurobiology, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Multistep-Ahead Forecasting of Chlorophyll Concentration Based on Dynamic Collaborative Attention Network - Lei Wang; Guodong Han; Ping Wu; Jie Mei; Zhenyu Lin; Shengming Cheng; Xianhua Wei; Xu Yang; Chuxu Xiong; Shaoyang Dai; Ying Zhao (Journal of Marine Science and Engineering, 2025)
Multistep-ahead forecasting of chlorophyll concentration is of great significance in red tide early warning systems. Existing methods often neglect the potential adverse interactions between non-predictive variables and chlorophyll while failing to fully utilize the effective information in historical decoder units. To address these issues, this paper proposes a Dynamic Collaborative Attention Network (DCAN) model for chlorophyll concentration forecasting, which consists of two components: a Two-Stage Variable Embedding Network (TSVEN) and a Dynamic Attention Network (DyAN). The TSVEN can identify the non-predictive variables that have the most significant impact on chlorophyll changes and generate corresponding spatial vectors from them, thereby alleviating the information conflict between chlorophyll and non-predictive variables. The DyAN integrates a context attention module and a filtering gate mechanism. The former effectively extends the forecasting time range by dynamically retrieving historical decoder states, while the latter selectively integrates historical decoder information, thereby improving the reliability of model decisions and prediction accuracy. Experimental results based on real datasets show that the proposed model outperforms the current state-of-the-art methods in chlorophyll concentration forecasting tasks and exhibits good interpretability.

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Grain size and geochemical evidence for the integration of the Yellow River through the Sanmen Gorge - Han Hu; Ziying Yu; Jiaxing Yang; Jiayi Lin; Wenjing Yang; Baofeng Li; Gang Hu; Xin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Redox-regulated plastoglobule ABC1K1–ABC1K3 kinase complex controls plastoquinone mobilization for chloroplast photosynthetic adaptation to red light - Mei Yang; Hao Huang; Chao Xu; Xue Han; Guochen Qin; Le Chang; Fang Lin; Xuncheng Wang; Hang He; Xing Wang Deng (Molecular Plant, 2025)

Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Deciphering the acute toxicity mechanisms of PFAS in algae: A molecular descriptor and binding energy hierarchy perspective - Yanting Li; Lin Zhao; Lu Wang; Han Zhang; Guodong Xing; Jinrui Yuan; Yongkui Yang; Peizhe Sun (Journal of Hazardous Materials, 2025)

In-situ remediation of Cr(VI) contaminated groundwater by synergistic oxalic acid-ethanol reduction: Mechanistic insights and sand tank validation - Wenwen Lin; Yang Liu; Zhonghui Han; Chengye Wang; Xiaoxu Zhang; Taigang Ma; Hejun Ren (Journal of Cleaner Production, 2025)

Nondestructive detection of biogenic amines in muscle of Chinese mitten crab (Eriocheir sinensis): A basis for quality assessment using infrared spectroscopy and deep learning - Qingli Han; Jianfeng Lu; Yuan Song; Yang Wang; Lin Lin; Zhi Zheng; Shaotong Jiang; Wenhua Miao; Chenghui Wang (Food Chemistry, 2025)

A new strategy with forming the aggregation unit to improve chlorophyll water solubility based on its natural inherent structure carriers - Zhaotian Yang; Jinghao Zhang; Suxia Shen; Ning Xu; Zixuan Han; Lin Zeng; Yan Zhang (Food and Bioproducts Processing, 2025)

Effect of the CuxNi1-xN bimetallic electrocatalyst on the ignition and combustion of electrically controlled solid propellants - Ziyang Han; Qiyang Wang; Huimin Nai; Haoyang Lu; Yingxue Ju; Jian Zhang; Debin Xia; Yulin Yang; Kaifeng Lin (Chemical Engineering Journal, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Theranostic nanoplatform for triple-negative breast cancer therapy: Autophagy suppression-coordinated siRNA delivery triggers apoptosis, ferroptosis, and pyroptosis via photothermal activation - Guobao Ning; Lishen Yang; Bilian Li; Jianghua Lin; Shufen Li; Fengqi Zhou; Han Chen; Xingye Zheng; Weijie Sun; Hui Zhao; Can-Peng Li (Chemical Engineering Journal, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Critical Buffer Zones (500–1000 m) for River Ecosystem Integrity: Scale-Dependent Land Use Impacts on Macrobenthos in the Tanghe River, China - Xiaoyue Lin; Xuemei Han; Jiading Yang; Fengyu Liu; Shujia Chang (International Journal of Environmental Research, 2025)

Can delivery riders act as informal guardians in crime prevention? - Shuli Zhou; Lin Liu; Han Yue; Kaiyin Yang; Jianjun Li; Guangwen Song (Applied Geography, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Spatiotemporal dynamics of sea ice volume and their potential drivers in Liaodong Bay, China, using Sentinel-3 data over five ice seasons - Hongkun Ling; Jialing Wang; Lintai Zheng; Yue Lin; Jiashen Tian; Zhen Wang; Zhichuang Lu; Jiabo Han; Wenhua Liu; Liangliang Yang (Marine Geodesy, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Reduction of antibiotics and antibiotic resistance genes in simulated-sunlight-supported counter-diffusion bacteria-Algae biofilms: Interface properties and functional gene responses - Han Zhang; Jiao Yin; Haotian Jiang; Weichen Zeng; Yufei Cheng; Jiaxuan Yang; Dachao Lin; Langming Bai; Heng Liang (Water Research, 2025)

Sustainable and safe biochar-based composites from ZIF-8 and artificial humic acid for enhanced environmental remediation of Cu(II) and tetracycline in water - Shuang Gai; Lin Han; Xinru Xu; Zhiyuan Feng; Fangjun Lou; Wenbo Liang; Fan Yang (Process Safety and Environmental Protection, 2025)

Feasibility study of the integration of buoyancy energy storage systems in floating offshore wind: A case study in Taiwan - Ting-Li Lin; Shun-Han Yang (Ocean Engineering, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Unraveling ozone formation sensitivity to ambient VOCs and NOx at urban and mountain sites in a typical city of eastern China - Xiaorong Zhang; Deming Han; Jiandong Shen; Feng Chen; Liuyan Cao; Jinhan Chen; Xu Lin; Yang Yang; Lin Yang; Wenjing Li; Xiaowei Qiao; Shuangxu Zhou; et al. (Environmental Pollution, 2025)

Acidification boosts the photodynamic activity of anthocyanidin for enhanced sterilization - Zhenqing Guo; Yajie Wang; Xinqi Wang; Ting Du; Kaiyuan Su; Lin Yang; Yaru Han; Shuo Shi; Jianlong Wang; Wentao Zhang (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

An in vivo NanoBiT-based pseudoviral biosensor for real-time monitoring of SARS-CoV-2 spike/hACE2 interactions and therapeutic screening - Cheng-Han Lin; Meng-Wei Lin; Xin-Rui Yang; Hua-Hsin Chiang; Ting-Hsuan Wu; Chin-Hung Tsai; Chih-Sheng Lin (Analytica Chimica Acta, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Corrigendum to “Along-strike variations in intermediate-depth seismicity in the southernmost Mariana subduction zone: Impact from the subduction of an oceanic plateau” [Tectonophysics, Volume 913, 27 October 2025, 230875, https://doi.org/10.1016/j.tecto.2025.230875] - Han Chen; Gaohua Zhu; Hongfeng Yang; Jiangyang Zhang; Shaopin Lu; Chuanxu Chen; Jian Lin; Yiming Luo (Tectonophysics, 2025)

Along-strike variations in intermediate-depth seismicity in the southernmost Mariana subduction zone: Impact from the subduction of an oceanic plateau - Han Chen; Gaohua Zhu; Hongfeng Yang; Jiangyang Zhang; Shaopin Lu; Chuanxu Chen; Jian Lin; Yiming Luo (Tectonophysics, 2025)

The potential of Cupriavidus sp. DF5525 degrading high concentrations of p-dichlorobenzene - Hong-Lin Ma; Ze-Shen Liu; Qun Han; Yi Yang; De-Feng Li (Journal of Hazardous Materials, 2025)

Light-driven CO2 reduction for acetate production by coupling photocatalyst CdS with acetogenic bacteria Clostridium aceticum: An insight into the electron transfer pathway - Bo Fu; Wei Lin; Hui Zhao; Shijian Yang; Jingyi Han; Qihao Cao; He Liu; Hongbo Liu; Jieshu Qian (Journal of Environmental Chemical Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Cobalt-functionalized sulfur-deficient MoS2: Unlocking enhanced Fenton-like activity via phase transformation and Co sites regeneration - Cunxin Lin; Na Wang; Sixun Li; Han Li; Jie Yang; Ziqiu Ren; Yunchen Du; Qun Xu (Chemical Engineering Journal, 2025)

A novel hydrogel electrolyte for self-powered sensing and safe energy storage systems in extreme environments - Wen Jiang; Yang Tao; Qiuxiang Yang; Yudong Wang; Lin Peng; Ce Zhang; Shounian Cheng; Jiandan Liang; Yu Han; Xia Cao (Chemical Engineering Journal, 2025)

Interfacial depassivation enables long-cycling silicon-based solid-state batteries without stack pressure - Lu Zhao; Junwei Han; Xin Qin; Qian Xu; Fei Yang; Junshu Sun; Pengcheng Dai; Lin Shi; Debin Kong; Linjie Zhi (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Deformation and Seepage Characteristics of Gassy Coal Subjected to Cyclic Loading–Unloading of Pore Pressure - Shugang Li; Chongzhi Wang; Bin Zhou; Haiqing Shuang; Haifei Lin; Shoujian Peng; Biao Hu; Han Yang; Hang Liu (Natural Resources Research, 2025)

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Multiple behaviour recognition of free-range broilers in cross-domain scenarios using MCA-YOLOv5 - Yang Guo; Junshu Wang; Peng Lin; Chengcheng Yin; Yuxing Han (Biosystems Engineering, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Olfactory dysfunction induced by pesticides: Adverse outcomes, emerging mechanisms, and risk for neurodegenerative diseases - Lin Wang; Si-Yang Liu; Han-Yue Zheng; Shou-Min Fang; Li Zhuo; Feng Xu; Quan-You Yu (Pesticide Biochemistry and Physiology, 2025)

Predicting arsenic bioaccessibility: A global data-driven machine learning approach and its implication for reducing carbon emissions - Haonan Zhang; Dan Han; Maosheng Zhong; Tianxiang Xia; Suo Yang; Shijie Wang; Ping Zhang; Lin Jiang (Journal of Hazardous Materials, 2025)

Toward more accurate quantification: A review of global large river basin management policies - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Zhen Hong; Ji-Wei Pang; Guene L. Razack; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2025)

Application of spectral induced polarization technique in monitoring zinc removal by activated carbon as a permeable reactive barrier material - Sheng Zhou; Yi-Xin Yang; Jing-Jing Cao; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Contaminant Hydrology, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Alleviating moxifloxacin-induced biological inhibition in ethanol and Cl− coexisted wastewater: Why UV/H2O2 is better than Fenton - Yingying Zhang; Min Yang; Wenbo Cui; Lin-Ji Xu; Depeng Zhang; Yu Tao; Jing-Long Han; Aijie Wang (Chemical Engineering Journal, 2025)

An efficient network with state space model under evidential training for fetal echocardiography standard view recognition - Changzhao Chen; Yiman Liu; Tongtong Liang; Shibin Lin; Xiaoxiang Han; Xiaohong Liu; Jing Yang; Yuqi Zhang; Xueping Yan (Medical & Biological Engineering & Computing, 2025)

Distinct responses of fungal and bacterial denitrification genes to seasonal changes, nitrogen deposition and precipitation reduction in subtropical forest soils - Qirun Chen; Fengyi Han; Maokui Lyu; Zhiwei Zeng; Yanjiang Cai; Yuheng Cheng; Zi-Yang He; Milin Deng; Jinsheng Xie; Yongxin Lin (Applied Soil Ecology, 2025)

Succession of biological soil crusts modifies patterns of soil eukaryotic communities along a precipitation gradient - Lin Xu; Yongping Kou; Xiangzhen Li; Chaonan Li; Jiabao Li; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengmin You; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2025)

PINN and KAN temperature prediction of carbon Fiber/Epoxy composite materials irradiated by nuclear environment simulated intense heat fluxes - Xiaoxiang Han; Jun Li; Lin Yuan; Xin Zhang; Weijie Zhu; Yang Liu; Haiyang Zhang; Boyu Wang (Annals of Nuclear Energy, 2025)

First and northernmost record of the invasive redhead cichlid (Vieja melanurus) in East Asia: evidence from Taipei City, Northern Taiwan - Yen-Ting Lin; Yu-Hsiang Lin; Jhao-Cian Hou; Hong-Yu Yang; Yu-San Han (Biological Invasions, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Geochemical remediation and spectral induced polarization monitoring of Cu2+ by geographically abundant paleosol and loess - Yi-Xin Yang; Sheng Zhou; Long-Long Meng; Lin-Han Wang; Chi Zhang; Bate Bate (Journal of Water Process Engineering, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

Experimental investigation on the interface of concrete-filled steel tubular (CFST) structures based on roughness and geometric deviation - Dan-Yang Ma; Ying-Qian Guo; Lin-Hai Han; Chuan-Chuan Hou (Engineering Structures, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Single-cell sequencing and spatial transcriptomics reveal FAS+ T cell and autophagy-related signatures predicting chemoimmunotherapy response in diffuse large B-cell lymphoma patients - Ning Lou; Liyuan Dai; Ruyun Gao; Jianliang Yang; Lin Gui; Sheng Yang; Peng Liu; Yuankai Shi; Xiaohong Han (Science China Life Sciences, 2025)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Design of heavy chain antibody-drug conjugates targeting c-Met to eradicate lung adenocarcinoma giant tumors with a single-dose - Wenjing Ning; Han Liu; Hongye Zeng; Xiaojing Qin; Lin Xu; Shiting Yang; Zhiren Zeng; Na Yuan; Zhenzhen Zhu; Xiaoqing Chen; Tao Xu; Fentian Chen; et al. (Science Bulletin, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Characteristics, immobilization of linoleic acid isomerase from Bifidobacterium breve and its application in rice bran oil - Lin Li; Ning Wang; Liqi Wang; Fuming Yang; Weining Wang; Yike Han; Dianyu Yu (Food Research International, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Novel ductile and durable engineered cementitious composite columns reinforced with steel-FRP composite bars: Axial compression behavior and design - Yulei Bai; Qipeng Ma; Shiwen Han; Lin Yang; Yufeng Zhang; Hongyu Zhang (Engineering Structures, 2025)

Performance of recycled aggregate concrete-filled high-strength steel tubular members under combined compression-bending-torsion - Zhi-Cheng Yang; Lin-Hai Han; Hua-Yang Zhao; Xiang-Yu Zhou (Engineering Structures, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Thermal-enhanced deep removal of multiple impurities upon pH induction towards selective regeneration of high-purity iron phosphate - Yaohui Xie; Fen Zhang; Shuyu Xiang; Guang Yang; Lin Qu; Fei Han; Liang Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

Cycleift: A deep transfer learning model based on informer with cycle fine-tuning for water quality prediction - Yang Yu; Shixin Zhao; Lintong Han; Lin Peng; Yanmei Xu; Qiujin Tian; Sen Chen; Zuogang Yang; Qiude Li; Zuquan Hu (Stochastic Environmental Research and Risk Assessment, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

Standing crop and size structure of phytoplankton are strongly regulated by the turbidity maximum in the macrotidal Qiantang River estuary-Hangzhou Bay - Lin Zhan; Yuanli Zhu; Chaoxiang Xu; Wei Du; Zhi Yang; Yulu Jiang; Kangning Jia; Ping Du; Chenhua Han; Wei Huang; Jiangning Zeng; Zhibing Jiang (Journal of Oceanology and Limnology, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Spatial-temporal modeling for urban climate: Enhancing energy prediction with global temporal convolutional attention networks - Yang Lin; Hoon Han; Christopher Pettit (Urban Climate, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Effects of green space exposure on acute respiratory illness in community-dwelling older people: A prospective cohort study - Qingwei Zhong; Lefei Han; Xinyue Ye; Lin Yang (Landscape and Urban Planning, 2025)

New insights into the impact of microplastics on nitrogen transformation in urban rivers based on field experiments - Cheng Yang; Yuanyuan Feng; Jinjiang Duan; Nayin Li; Qingping Zou; Peng Lin; Mengli Chen; Jiang Li; Han Zhang (Journal of Environmental Chemical Engineering, 2025)

Quasi-Solid-State Electrolytes: Bridging the gap between solid and liquid electrolytes for zinc-ion batteries - Tao Xue; Jinpeng Guan; Yongbiao Mu; Meisheng Han; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

Freestanding vanadium oxides/carbon hybrid cathode with long-term cyclability at low current density for flexible aqueous zinc ion batteries - Zhouyang Qin; Gaoxu Han; Yilin Yang; Shengle Hao; Lingxiao Yu; Yuxiao Lin; Yunsong Li; Ruitao Lv; Wanci Shen; Feiyu Kang; Zheng-Hong Huang (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Effects of bulk-rock chemistry on paragonite stability in high-pressure epidote-amphibolites from the Yuli metamorphic belt, Taiwan - Wen-Han Lo; Chin-Ho Tsai; Ioannis Baziotis; Sun-Lin Chung; Chiao Liu; Yoshiyuki Iizuka; Hao-Yang Lee (Contributions to Mineralogy and Petrology, 2025)

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

RAPID LEAF FALLING 1 facilitates chemical defoliation and mechanical harvesting in cotton - Bing Zhang; Dandan Yue; Bei Han; Danfan Bao; Xiao Zhang; Xuyang Hao; Xin Lin; Keith Lindsey; Longfu Zhu; Shuangxia Jin; Maojun Wang; Haijiang Xu; et al. (Molecular Plant, 2025)

Seismic performance of grouted CFDST column base: Investigation and design method - Zhi-Cheng Yang; Wei Li; Yu-Feng Cheng; Lin-Hai Han (Engineering Structures, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Immune dysregulation of decidual NK cells mediated by GRIM19 downregulation contributes to the occurrence of recurrent pregnancy loss - Ying Wang; Anliang Guo; Lin Yang; Xiaojuan Han; Qianni Li; Jin Liu; Yilong Han; Yang Yang; Lan Chao (Molecular and Cellular Biochemistry, 2025)

Mechanical response of broken surrounding rock by in-situ expansion of highway tunnel - Hongyun Yang; Jiang Gao; Yongchao Ding; Xiang Chen; Zhi Lin; Han Wu; Yongke Wei; Longwang Xu; Zhanfeng Yang (Bulletin of Engineering Geology and the Environment, 2025)

Aerosol particles released from grit chambers of nine urban wastewater treatment plants in typical regions: Fugitive characteristics, quantitative drivers, and generation process - Wenwen Wang; Kaixiong Yang; Lin Li; Yunping Han (Water Research, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

T-2 toxin induces cardiac fibrosis by causing metabolic disorders and up-regulating Sirt3/FoxO3α/MnSOD signaling pathway-mediated oxidative stress - Lichun Qiao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jingming Zhan; Feidan Deng; Miaoye Bao; Huifang He; Xinyue Wen; Huan Deng; Xining Wang; Yujie He; et al. (Journal of Environmental Sciences, 2025)

Exploring dialkyl carbonate as a low-carbon fuel for combustion engines: an overview - Guofeng Yang; Qingxuan Wang; Lincheng Li; Delin Lyu; He Lin; Dong Han (Fuel, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Simulated nitrogen deposition enhances resistance of female poplars over males to Pestalotiopsis microspora infection through the recruitment of antagonistic microbes in phyllosphere - Guoqing Zhu; Shuya Yang; Wanci He; Xiaotao Han; Lianghua Chen; Gang Chen; Tiantian Lin (Journal of Environmental Management, 2025)

Reconstruction of aeolian sand processes at different scales utilizing the Scale-Independent Particle Tracking Velocimetry - Kaiyuan Guan; Yang Zhang; Xu Han; Yuanwei Lin; Xin Gao; Bin Yang (Geomorphology, 2025)

Soil phosphorus dynamics and its correlation with ectomycorrhizal fungi following forest conversion in subtropical conifer (Picea asperata) forests - Lixia Wang; Shiyu Song; Huichao Li; Yang Liu; Lin Xu; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; Zhenfeng Xu; Li Zhang; et al. (European Journal of Soil Biology, 2025)

Atmospheric black carbon (BC) in Hangzhou, China: Temporal variation, source apportionment, and case study of the 19th Asian Games - Jian Lin; Deming Han; Feng Chen; Xiaorong Zhang; Yang Yang; Lin Yang; Hua Guo; Zechen Yu; Liuyan Cao; Jianbo Shi; Guibin Jiang (Environmental Pollution, 2025)

Analytical behaviour of concrete-encased concrete-filled steel tubular (CFST) member under combined compression and shear load - Zhi-Cheng Yang; Lin-Hai Han; Wei Li (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A bioengineered antibody conjugate reshape dendritic cell viability for immune-tolerance modulation - Xiaoqing Chen; Yalin Wang; Tao Xu; Han Liu; Xinya Ye; Peng Wang; Xiaojing Qin; Shiting Yang; Wenjing Ning; Hongye Zeng; Lin Xu; Mujin Fang; et al. (Chemical Engineering Journal, 2025)

Synthesis and antitumor activity of ultra-low molecular weight hyaluronic acid-decorated camptothecin conjugates - Changsheng Chen; Henan Zhang; Jingjun Han; Lin Yang; Shuang Li; Qingwen Jia; Junqiang Fang; Peixue Ling; Shuaishuai Wang (Carbohydrate Polymers, 2025)

Three-Dimensional Lattice Modeling of Interaction Behavior Between Hydraulic Fractures and Natural Fractures with Varied Morphologies in Hot Dry Rock - Song Wang; Luqing Zhang; Lin Cong; Jian Zhou; Duoxing Yang; Xiufeng Zhang; Zhenhua Han (Rock Mechanics and Rock Engineering, 2025)

Comammox Nitrospira and ammonia-oxidizing bacteria are metabolically active in a subtropical estuarine wetland - Mengmeng Feng; Yongxin Lin; Guiping Ye; Zi-Yang He; Dong Zhu; Hang-Wei Hu; Yuheng Cheng; Fengyi Han; Ping Yang; Ji-Zheng He (Applied Soil Ecology, 2025)

Enrichment mechanisms of natural hydrogen and predictions for favorable exploration areas in China - Shuai Wang; Shu Jiang; Xuelian Huang; Shihua Qi; Jingyu Lin; Yongjie Han; Yang Wang; Xueqing Wu; Guodong Zheng (Applied Geochemistry, 2025)

Fucoxanthin ameliorates ulcerative colitis by maintaining the epithelial barrier via blocking JAK2/STAT3 signaling pathway - Jingjing Ma; Simei Yue; Yinghui Liu; Lingjiao Gong; Pengzhan He; Yingjie Yang; Zhengxin Fu; Danxiang Han; Qiang Hu; Fei Liao; Lin Xu (Toxicology and Applied Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Optimization of the life cycle environmental impact of shell powder and slag concrete using response surface methodology - Yi Han; Bo Yang; Li-Yi Meng; Hyeong-Kyu Cho; Runsheng Lin; Xiao-Yong Wang (Process Safety and Environmental Protection, 2025)

Non-additive effects of leaf-litter flammability on eight subtropical tree species: Implications for forest species composition and fire susceptibility - Pujie Wei; Li Tang; Zixuan Xiong; Byron B. Lamont; Lin Chen; Weixing Xue; Zeyao Zhao; Wenxiong Lu; Jisi Han; Wanwan He; Wei Yang; Zhaogui Yan (Journal of Environmental Management, 2025)

A kinetic study of CO2 and H2O addition on NO formation for ammonia-methanol combustion - Yuzheng Gao; Youping Li; Xianting Wei; Yang Zheng; Shixuan Yang; Qirong Yang; Han Jiang; Yiran Zhang; He Lin (Fuel, 2025)

DTD1 modulates synaptic efficacy by maintaining D-serine and D-aspartate homeostasis - Xiao Liu; Chaojuan Yang; Zhuoran Lin; Jianing Li; Bin Yin; Xuepei Lei; Wei Han; Boqin Qiang; Pengcheng Shu; Chen Zhang; Xiaozhong Peng (Science China Life Sciences, 2025)

Rapid screening of pottery lipid residue profile via comprehensive two-dimensional gas chromatography - Bin Han; Nanning Lyu; Long Yan; Tao Wang; Jie Gao; Liugen Lin; Huiyun Rao; Yimin Yang (Analytica Chimica Acta, 2025)

Experimental investigation on the soil arching effect induced by deep-buried shield tunneling - Ren-Peng Chen; Xu Song; Fan-Yan Meng; Han-Lin Wang; Yang Liu; Lei Wen (Tunnelling and Underground Space Technology, 2025)

Coupling phylogenetic relatedness and distribution patterns provides insights into sandburs invasion risk assessment - Ming Yang; Yuhan Qi; Xiaoqing Xian; Nianwan Yang; Lin Xue; Chi Zhang; Han Bao; Wanxue Liu (Science of The Total Environment, 2025)

A bottom-up nationwide analysis of sectoral land use reveals spatial heterogeneity across the United States - Zhixiu Han; Wei Xie; Yiru Song; Lin Sun; Huajun Yu; Bin Chen; Yang Li; Yutao Wang (Resources, Conservation and Recycling, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

Pyramid-Matrix-like buried interface construction for Boosting the photovoltaic performance of perovskite solar cells - Xin Luan; Ying Han; Mengyao Sun; Yingjie Wang; Le Zhang; Yuhuan Song; Fengyou Wang; Lin Fan; Xin Qu; Xiaoyan Liu; Lili Yang (Chemical Engineering Journal, 2025)

Triboelectric materials with UV protection, anti-bacterial activity, and green closed-loop recycling for medical monitoring - Jiandan Liang; Qiuxiang Yang; Ce Zhang; Wen Jiang; Shounian Cheng; Yang Tao; Lin Peng; Yu Han; Xia Cao; Zhong Lin Wang (Chemical Engineering Journal, 2025)

Supplementation with probiotics co-cultivation improves the reproductive performance in a sow-piglet model by mother-infant microbiota transmission and placental mTOR signaling - Suchen Li; Tingting Lu; Zhixin Lin; Yuanyuan Zhang; Xinchen Zhou; Meng Li; Hui Miao; Zhiren Yang; Xinyan Han (World Journal of Microbiology and Biotechnology, 2025)

Seasonal variation modifies the composition and co-occurrence network of the abundant and rare fungal groups in a seasonally frozen ground - Jianfei Guan; Yang Cao; Hongjia Xu; Lin Han; Mengyang You; Xuechen Yang (Journal of Soils and Sediments, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Multi-omics analysis of the toxic effects on gill tissues of crucian carp (Carassius auratus) from chronic exposure to environmentally relevant concentrations of Di(2-ethylhexyl) phthalate (DEHP) - Yang Yang; Yingjie Liu; Song Wu; Lin Han; Yanchun Sun (Science of The Total Environment, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Risk hotspots and influencing factors identification of heavy metal(loid)s in agricultural soils using spatial bivariate analysis and random forest - Xiaohang Xu; Zhidong Xu; Longchao Liang; Jialiang Han; Gaoen Wu; Qinhui Lu; Lin Liu; Pan Li; Qiao Han; Le Wang; Sensen Zhang; Yanhai Hu; et al. (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Impacts of distinct residual aluminum on gypsum scaling in nanofiltration: Identification of key species - Jinjin Jia; Jinlong Wang; Dachao Lin; Jing Zhao; Hesong Wang; Longfeng Hu; Jiaxuan Yang; Han Zhang; Guibai Li; Heng Liang (Desalination, 2024)

Covalent metal–organic porous polymer on ZIF-67 realize anti-UV and highly stressed flame retardant epoxy composites - Jin Cao; Shangxian Chen; Zhengde Han; Ye-Tang Pan; Yichao Lin; Wei Wang; Rongjie Yang (Chemical Engineering Journal, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Enhanced therapeutic potential of Flotillins-modified MenSCs by improve the survival, proliferation and migration - Fangfang Cheng; Longkai Ji; Pan Li; Zhisheng Han; Yanan He; Fen Yang; Zhihao Xu; Yonghai Li; Tao Ruan; Xinxing Zhu; Juntang Lin (Molecular Biology Reports, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Similarity characterization of geotechnical engineering sites under the site-specific data scenario - Liang Han; Mingjing Jiang; Wengang Zhang; Lin Yang (Bulletin of Engineering Geology and the Environment, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

The Temperature-Dependent Monotonic Mechanical Characteristics of Marine Sand–Geomembrane Interfaces - Zhiming Chao; Hongyi Zhao; Hui Liu; Peng Cui; Danda Shi; Hai Lin; Yang Lu; Bing Han; Shuang Chen (Journal of Marine Science and Engineering, 2024)
The utilization of geomembrane reinforcement technology is pervasive in marine sand foundation reinforcement projects. However, the elevated temperatures and intricate stress conditions prevalent in marine environments exert a notable influence on the mechanical characteristics of geomembrane interfaces comprising marine sand, which impedes the efficacy of geomembrane reinforcement in marine sand foundations. Nevertheless, there is a lack of research investigating the temperature-dependent interfacial mechanical performance of geomembranes and marine sand under diverse stress states. In this study, a series of monotonic shear tests were carried out on the interface between geomembranes and marine sand within a temperature range of 5 °C to 80 °C. These experiments were carried out using a self-developed large-scale temperature-controlled interfacial dynamic and static shear device. The experimental results demonstrate that temperature has a pronounced effect on the monotonic mechanical characteristics of the geomembrane–marine sand interface, which displays clear temperature dependence. The findings of this study may help in the design and optimization of offshore projects where a marine sand–polymer layer interface exists.

Comprehensive evaluation of the nephrotoxicity of carbon quantum dots: Effects of the surface charge - Pei-Luen Jiang; Yan-Yu Hong; Lingyan Yang; Han-Jia Lin; Chih-Ching Huang; Yan-Hua Chen; Chia-Hua Lin; Yi-Chun Chen (Chemosphere, 2024)

Rapid and accurate detection of total nitrogen in the different types for soil using laser-induced breakdown spectroscopy combined with transfer learning - Peng Lin; Changbo Song; Chongshan Yang; Mengjie Zhang; Shixiang Ma; Jiangtao Wen; Daming Dong; Yuxing Han (Computers and Electronics in Agriculture, 2024)

Structural determinants of parabens in inhibiting human and rat gonadal 3β-hydroxysteroid dehydrogenase - Chentao Ding; He Zhu; Yunbing Tang; Yingfen Ying; Yang Zhu; Han Lin; Ren-Shan Ge; Huitao Li (Toxicology and Applied Pharmacology, 2024)

Application of a novel machine learning model for the prediction and optimization of anti-blast performance of sandwich honeycomb blast walls - Lei Yang; Hong Lin; Longcheng Wei; Chang Han; Hao Xu; Hassan Karampour (Ocean Engineering, 2024)

Influence of perfluorooctanoic acid on alkaline anaerobic fermentation of waste activated sludge: Perspective from volatile fatty acids production and sludge reduction - Zhilin Zhao; Xiaoying Zheng; Shanshan Yang; Haidong He; Zongshuo Han; Wenfei Li; Tao Lin; Hang Xu (Journal of Environmental Management, 2024)

Multi-active photocatalysts of biochar-doped g-C3N4 incorporated with polyoxometalates for the high-efficient degradation of sulfamethoxazole - Fang Yang; Lihe Zhu; Zushen Xu; Yongwei Han; Xue Lin; Junyou Shi; Zhong Sun; Xixin Duan (Environmental Pollution, 2024)

Oceanic response to tropical cyclone in the northern South China Sea observed by underwater gliders during 2018 and 2020 - Yanfeng Zhang; Han Zhang; Xiaodong Tang; Shaoqiong Yang; Yanhui Wang; Xiayan Lin; Di Tian; Dake Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Reducing defects in hard carbon graphite domain: Employing a fully dynamic bonding with a multi-crosslinked biomass-based binder for enhanced sodium ion storage - Jiaqi Jiao; Han Lu; Conghua Yi; Dongjie Yang; Xuezhi Zeng; Jinxin Lin; Hongqiang Li (Chemical Engineering Journal, 2024)

Enhancement of stress resistance of electroactive biofilms against hypersaline shock via exogenous electron mediator addition - Tao Li; Chen-ying Li; Han-lin Liang; Xiao-xue Li; Xiao-li Yang; Hua Li; Hai-liang Song (Chemical Engineering Journal, 2024)

Spatial distribution characteristics and influencing factors of soil organic carbon based on the geographically weighted regression model - Xin Shu; Liangmin Gao; Jinxiang Yang; Jieyu Xia; Han Song; Limei Zhu; Kai Zhang; Lin Wu; Zhendong Pang (Environmental Monitoring and Assessment, 2024)

Warming mitigates the effects of nitrogen addition on the soil diazotrophic community in a subtropical forest - Jiling Cao; Lin Li; Yu Han; Zhiyuan Liu; Faying Lai; Yusheng Yang (Applied Soil Ecology, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

Ensuring Clinical Excellence: The Mindray SAL9000 Biochemical Immunoassay System - Zhenzhen Zou; Honghui Tang; Erya Xiao; Yu Zhou; Xuebei Yin; Zhen Hu; Yang Cai; Qingzhen Han; Lin Wang (Cell Biochemistry and Biophysics, 2024)

Structural disruption in subjective cognitive decline and mild cognitive impairment - Jie Song; Han Yang; Hailang Yan; Qian Lu; Lei Guo; Hui Zheng; Tianjiao Zhang; Bin Lin; Zhiyong Zhao; Chuan He; Ying Shen (Brain Imaging and Behavior, 2024)

Mineralogy and geochemistry of the Cambrain Shuijingtuo Formation black shales from Western Hubei, China: implications on enrichment of critical metals and paleoenvironment - Yuan Wang; Jing Li; Yang Lin; Xinguo Zhuang; Vanlong Hoang; Peng Wu; Xin Luo; Han Zhang; Xiaoyang Zhang (Frontiers in Marine Science, 2024)
Black shales have attracted the attention of numerous researchers not only due to their high potential as hydrocarbon source rocks and shale gas reservoirs, but also to the enrichment of critical metal elements in black shale series. Black shale of the Cambrian Shuijingtuo Formation is one of the most important black shales in the Yangtze platform. This paper conducts integrated research on the mineralogical and geochemical characteristics of this black shale from the Luojiacun section in Western Hubei Region, aiming at elaborating the enrichment mechanism of elevated critical metal elements in the Shuijingtuo black shale. Minerals in the Shuijingtuo black shale are predominantly composed of quartz (avg. 43.0%) and clay minerals (avg. 32.5%), with small proportions of calcite, albite, clinochlore, and pyrite. The Shuijingtuo black shale is characterized by high total organic carbon (TOC, avg. 3.9%) content and enriched in V-Ni-Cr-U and Sr-Ba critical metal assemblages. The elevated V, Cr, Ni, and U present dominant organic affinities, while Sr and Ba are closely correlated to calcite and pyrite, respectively. The enrichment of V-Cr-Ni-U critical element assemblages in Shuijingtuo black shale are ascribed to the high primary productivity, anoxic depositional conditions, marine biologic production, and low-temperature hydrothermal activities. The enrichment of Sr and Ba is related to the high primary productivity and anoxic depositional conditions, respectively.

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Field performance of 15 rain gardens in different cities in Taiwan - Chi-Feng Chen; Yi-Wei Chen; Cheng-Han Lin; Jen-Yang Lin (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Determination of 3-nitropropionic acid in sugarcane using dispersive solid-phase extraction and gas chromatography–atmospheric pressure chemical ionization–tandem mass spectrometry - Zuolong Yu; Yu Lin; Xiujin Zhou; Yao Chen; Zhijin Yang; Chao Han; Yan Shen (Food Chemistry, 2024)

Supplementation with a phenolic-rich fraction from Ilex kudingcha improves inflammatory stress, gastrocnemius weights, and foreleg muscle grip strength in murine squamous cell carcinoma (SCC7)-bearing mice - Han-Chen Chao; Wan-Li Yang; Li-Wha Wu; Jin-Yuarn Lin (Food Bioscience, 2024)

The role of rhamnolipids in the growth and defense responses of passion fruit plants - Ting Yang; Jihu Li; Yongkai Mao; Han Wu; Mingjiang Lin; Lijuan Chen (Physiology and Molecular Biology of Plants, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Biocontrol potential of Bacillus velezensis QF-2 isolated from rhizosphere soil of Vickifunkia tianschanica - Tong Shen; Lei Zhang; Zhi-Han Ma; Zheng Gong; Hui-Ming Qi; Hong-Ying Yang; Yi-Lin He (Physiological and Molecular Plant Pathology, 2024)

Experimental investigation and intelligent control of the magnus anti-rolling device for ship stability at zero speed - Jianfeng Lin; Shizhao Wang; Yang Han; Hua-Dong Yao; Yumin Su (Ocean Engineering, 2024)

Farmland’s silent threat: Comprehensive multimedia assessment of micropollutants through non-targeted screening and targeted analysis in agricultural systems - Yang Qiu; Lijun Liu; Caifei Xu; Bo Zhao; Hang Lin; He Liu; Weixuan Xian; Han Yang; Rui Wang; Xingjian Yang (Journal of Hazardous Materials, 2024)

Xanthohumol combined with chitosan-oxidized starch film as a potential new strategy for food packaging: Characterization, physicochemical and biological properties - Fan Yang; Siyuan Chang; Lin Zhao; Jing Han; Hao Li; Sen Zhang; Sheng Guo; Jinao Duan (Food Packaging and Shelf Life, 2024)

High-rate pig manure substitution enhances comammox Nitrospira abundance and diversity in the Cinnamomum camphora coppice planting soils - Luyuan Sun; Jie Zhang; Jia Liu; Jiao Zhao; Ting Zhang; Fengyi Han; Zi-Yang He; Yongxin Lin (European Journal of Soil Biology, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

Global quantitative synthesis on the patterns and drivers of funneling ratio and enrichment ratio for stemflow - Meng-Di Wu; Zhi-Yun Jiang; Xiao Yang; Buerlan Yeerbolati; Lin Huang; Ying-Yin Zhong; Han-Wen Zhang; Xiao-Yan Li (CATENA, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Multiscale coupling analysis and modeling of airflow and heat transfer for warehouse-packaging-kiwifruit under forced-air cooling - Qian Chen; Jianping Qian; Han Yang; Jiali Li; Xintao Lin; Baogang Wang (Biosystems Engineering, 2024)

Straw returning and nitrogen reduction: Strategies for sustainable maize production in the dryland - Miaomiao Zhang; Ning Yang; Shiguang Wang; Xiaoqing Han; Pengfei Dang; Guoqing Li; Shuyue Wen; Lin Zhang; Jiquan Xue; Xiaoliang Qin; Kadambot H.M. Siddique (Journal of Environmental Management, 2024)

Activation energy and organic matter structure characteristics of shale kerogen and their significance for the in-situ conversion process of shale oil - Wenxue Han; Xia Luo; Shizhen Tao; Senhu Lin; Jinzhong Liu; Yanting Yang (Fuel, 2024)

Effects of Salt Content and Freeze-Thaw Conditions on Dynamic characteristics and its microscopic mechanism of Chloride Silty Clay - Yaqin Zhang; Ping Yang; Lin Li; Ting Zhang; Linliang Han (Cold Regions Science and Technology, 2024)

A leaf age‐dependent light use efficiency model for remote sensing the gross primary productivity seasonality over pantropical evergreen broadleaved forests - Jie Tian; Xueqin Yang; Wenping Yuan; Shangrong Lin; Liusheng Han; Yi Zheng; Xiaosheng Xia; Liyang Liu; Mei Wang; Wei Zheng; Lei Fan; Kai Yan; et al. (Global Change Biology, 2024)
Tropical and subtropical evergreen broadleaved forests (TEFs) contribute more than one‐third of terrestrial gross primary productivity (GPP). However, the continental‐scale leaf phenology‐photosynthesis nexus over TEFs is still poorly understood to date. This knowledge gap hinders most light use efficiency (LUE) models from accurately simulating the GPP seasonality in TEFs. Leaf age is the crucial plant trait to link the dynamics of leaf phenology with GPP seasonality. Thus, here we incorporated the seasonal leaf area index of different leaf age cohorts into a widely used LUE model (i.e., EC‐LUE) and proposed a novel leaf age‐dependent LUE model (denoted as LA‐LUE model). At the site level, the LA‐LUE model (average R 2 = .59, average root‐mean‐square error [RMSE] = 1.23 gC m −2 day −1 ) performs better than the EC‐LUE model in simulating the GPP seasonality across the nine TEFs sites (average R 2 = .18; average RMSE = 1.87 gC m −2 day −1 ). At the continental scale, the monthly GPP estimates from the LA‐LUE model are consistent with FLUXCOM GPP data ( R 2 = .80; average RMSE = 1.74 gC m −2 day −1 ), and satellite‐based GPP data retrieved from the global Orbiting Carbon Observatory‐2 (OCO‐2) based solar‐induced chlorophyll fluorescence (SIF) product (GOSIF) ( R 2 = .64; average RMSE = 1.90 gC m −2 day −1 ) and the reconstructed TROPOspheric Monitoring Instrument SIF dataset using machine learning algorithms (RTSIF) ( R 2 = .78; average RMSE = 1.88 gC m −2 day −1 ). Typically, the estimated monthly GPP not only successfully represents the unimodal GPP seasonality near the Tropics of Cancer and Capricorn, but also captures well the bimodal GPP seasonality near the Equator. Overall, this study for the first time integrates the leaf age information into the satellite‐based LUE model and provides a feasible implementation for mapping the continental‐scale GPP seasonality over the entire TEFs.

Research on semantic segmentation algorithm of high latitude urban river ice based on deep transfer learning - Wangyuan Zhao; Yanzhuo Xue; Fenglei Han; Xiao Peng; Yiming Zhao; Jiawei Zhang; Jianfeng Yang; Qi Lin; Yuliang Wu (International Journal of Remote Sensing, 2024)

Disinfectant-induced ammonia oxidation disruption in microbial N-cycling process in aquatic ecosystem after the COVID-19 outbreak - Lutong Yang; Ping Han; Qiaojuan Wang; Hui Lin; Donglin Wang; Jie Mao; Weixiao Qi; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

BaO-modified finger-like nickel-based anode for enhanced performance and durability of direct carbon solid oxide fuel cells - Lin Li; Yujiao Xie; Tingting Han; Jinjin Zhang; Fangyong Yu; Gen Li; Jaka Sunarso; Naitao Yang; Yongdan Li (Fuel, 2024)

Ultrathin-FeOOH-coated MnO2 nanozyme with enhanced catalase-like and oxidase-like activities for photoelectrochemical and colorimetric detection of organophosphorus pesticides - Maoding Zuo; Yuncong Yang; Su Jiang; Chenyu Zhu; Yun Han; Juan Hu; Kewei Ren; Lin Cui; Chun-Yang Zhang (Food Chemistry, 2024)

Optimized DLP 3D-printed high-resolution nano zirconia-hydroxyapatite scaffold with craniomaxillofacial soft tissue invasion resistance and pro-osteogenic properties via dectin-1/syk inflammatory axis - Xiaomeng Gao; Jieting Yang; Xuejing Gan; Yixiong Lin; Jieyun Xu; Zhengjie Shan; Zongpu Han; Shijie Chen; Baoxin Huang; Bingfeng Fan; Zetao Chen (Chemical Engineering Journal, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Diagnosis of the accuracy of land cover classification using bootstrap resampling - Tong Yang; Binghong Han; Xiaofei He; Ziqi Ye; Yongli Tang; Jiexin Lin; Xia Cui; Jian Bi (International Journal of Remote Sensing, 2024)

Structurally diverse 1,2-diarylpropanes from the fruit of Crataegus pinnatifida and the investigation on their mirror-image ECD spectra with the same absolute configurations - Tian-Ming Lv; Rui Guo; Bo-Han Yang; Peng Zhao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Species selection as a key factor in the afforestation of coastal salt-affected lands: Insights from pot and field experiments - Tzu-Hao Su; Yang Shen; Yao-Yu Chiang; Yu-Ting Liu; Han-Ming You; Hung-Chih Lin; Kuan-Ning Kung; Yao-Moan Huang; Chih-Ming Lai (Journal of Environmental Management, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

From theory to practice: Dissociation of AsMA under reactive metal perturbations for the harmlessness and resourcefulness of copper slag - Xingyuan Wan; Kaixi Jiang; Ting'an Zhang; Kun Wang; Han Yang; Shengnan Lin (Chemical Engineering Journal, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Continuous microalgal culture module and method of culturing microalgae containing macular pigment - Meng-Wei Lin; Chih-Sheng Lin; Yu-Tso Chen; Shao-Qian Huang; Yi-Chun Yang; Wen-Xin Zhang; Wei-Hong Chiu; Cheng-Han Lin; Chiu-Mei Kuo (Bioresource Technology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

In vivo transgenic studies confirm the critical acylation function of LeBAHD56 for shikonin in Lithospermum erythrorhizon - Liu Yang; Changyi Wang; Xiaohui Lai; Suo Jin; Xuan Wang; Zhongling Wen; Minkai Yang; Aliya Fazal; Yuhang Ding; Zhongyi Li; Jinfeng Cai; Guihua Lu; et al. (Plant Cell Reports, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Environmental and economic analysis of the transformation of paper mill sludge treatment technologies in China - Yanfei Lin; Guoxia Wei; Hanqiao Liu; Kai Li; Yuwen Zhu; Qianlong Han; Yunzhen Yang; Yi Lian (Environmental Science and Pollution Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

Association of blood cadmium levels and all-cause mortality among adults with rheumatoid arthritis: The NHANES cohort study - Haobiao Liu; Mian Liu; Lichun Qiao; Zhihao Yang; Yujie He; Miaoye Bao; Xue Lin; Jing Han (Journal of Trace Elements in Medicine and Biology, 2024)

Occurrence and spatiotemporal distribution of natural and synthetic steroid hormones in soil, water, and sediment systems in suburban agricultural area of Guangzhou City, China - Hang Lin; Liangzhuo Zhou; Shudong Lu; Han Yang; Yongtao Li; Xingjian Yang (Journal of Hazardous Materials, 2024)

Manure replacing synthetic fertilizer improves crop yield sustainability and reduces carbon footprint under winter wheat–summer maize cropping system - Jincan Niu; Qudsia Saeed; Wenning Wang; Runze Zhang; Lin Liu; Fenglian Lv; Jiaxing Xu; Yan Han; Panxin Zhang; Changlu Hu; Hu Xu; Benhua Sun; et al. (Journal of Environmental Management, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Decreased snow depth inhibits litter decomposition via changes in litter microbial biomass and enzyme activity - Ting Du; Li Zhang; Yulian Chen; Yu Zhang; Hemeng Zhu; Zhenfeng Xu; Bo Tan; Chengming You; Yang Liu; Lixia Wang; Sining Liu; Hongwei Xu; et al. (Science of The Total Environment, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Recycling of waste polyethylene in asphalt and its performance enhancement methods: A critical literature review - Hui Li; Yuzhao Han; E Guangxun; Yang Sun; Lei Wang; Xufei Liu; Jiaxing Ren; Zhijie Lin (Journal of Cleaner Production, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

Ascertaining sensitive exposure biomarkers of various metal(loid)s to embryo implantation - Mengyuan Ren; Tianxiang Wu; Shuo Yang; Ning Gao; Changxin Lan; Han Zhang; Weinan Lin; Shu Su; Lailai Yan; Lili Zhuang; Qun Lu; Jia Xu; et al. (Environmental Pollution, 2024)

Chromosomal mapping of a major genetic locus from Agropyron cristatum chromosome 6P that influences grain number and spikelet number in wheat - Yida Lin; Shenghui Zhou; Wenjing Yang; Bing Han; Xuezhong Liang; Yuxin Zhang; Jinpeng Zhang; Haiming Han; Baojin Guo; Weihua Liu; Xinming Yang; Xiuquan Li; et al. (Theoretical and Applied Genetics, 2024)

Slc43a2+ T cell metastasis from spleen to brain in RGNNV infected teleost - Qing Wang; Yali Liu; Minlin Zhang; Min Yang; Jiantao Liang; Xiaoling Zuo; Shaowen Wang; Xianze Jia; Huihong Zhao; Han Jiang; Qiang Lin; Qiwei Qin (Science China Life Sciences, 2024)

Sea Cucumber Viscera Contains Novel Non-Holostane-Type Glycoside Toxins that Possess a Putative Chemical Defense Function - Yanfang Liu; Zhen Lu; Zhi Yan; Ainuo Lin; Shaoshuai Han; Yaxi Li; Xiao Yang; Xiaodong Li; Xiuli Yin; Ranran Zhang; Ke Li (Journal of Chemical Ecology, 2024)

Post-stroke Chinese pure alexia: linguistic features and neuropsychological profiles - Shen-yi Kuang; Yi Xu; Yu-yuan Wang; Zi-gao Wang; Qiang Dong; Xiang Han; Shi-Lin Yang (Acta Neurologica Belgica, 2024)

Artificial humic acid coated ferrihydrite strengthens the adsorption of phosphate and increases soil phosphate retention - Shuang Gai; Bing Liu; Yibo Lan; Lin Han; Yixiong Hu; Guanghao Dongye; Kui Cheng; Zhuqing Liu; Fan Yang (Science of The Total Environment, 2024)

Significance of phosphate adsorbed on the cellular surface as a storage pool and its regulation in marine microalgae - Xian-Yang Zhang; Zhuo-Fan Li; Hai-Feng Gu; Ai-Qin Han; Feng-Xian Han; Lin-Jian Ou (Marine Environmental Research, 2024)

UV-induced photodegradation of emerging para-phenylenediamine quinones in aqueous environment: Kinetics, products identification and toxicity assessments - Wei Wang; Guodong Cao; Jing Zhang; Han Qiao; Huankai Li; Biwei Yang; Yanyan Chen; Lin Zhu; Yuecheng Sang; Lei Du; Zongwei Cai (Journal of Hazardous Materials, 2024)

Aboveground plants determine the exchange of pathogens within air-phyllosphere-soil continuum in urban greenspaces - Changyi Lu; Zufei Xiao; Hu Li; Ruixia Han; Anqi Sun; Qian Xiang; Zhe Zhu; Gang Li; Xiaoru Yang; Yong-Guan Zhu; Qing-Lin Chen (Journal of Hazardous Materials, 2024)

Experimental verification of seismic vibration control of high-rise buildings with friction-type multiple tuned mass dampers - Ging-Long Lin; Chi-Chang Lin; Tsung-Han Yang; Hao-Yu Lung (Engineering Structures, 2024)

A study on visual impact assessment of the enclosing wall entourage of Chinese traditional private garden - Zhongjv Yang; Chenping Han; Tao Gu; Lin Zhang; Guanjun Li; Jingjing Zhao; Xing Huang (Environmental Impact Assessment Review, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

An Improved VO Method for Collision Avoidance of Ships in Open Sea - Mao Zheng; Kehao Zhang; Bing Han; Bowen Lin; Haiming Zhou; Shigan Ding; Tianyue Zou; Yougui Yang (Journal of Marine Science and Engineering, 2024)
In order to effectively deal with collisions in various encounter situations in open water environments, a ship collision avoidance model was established, and multiple constraints were introduced into the velocity obstacle method, a method to determine the ship domain by calculating the safe distance of approach was proposed. At the same time, the ship collision avoidance model based on the ship domain is analyzed, and the relative velocity set of the collision cone is obtained by solving the common tangent line within the ellipse. The timing of starting collision avoidance is determined by calculating the ship collision risk, and a method for ending collision avoidance is proposed. Finally, by comparing the simulation experiments of the improved algorithm with those of the traditional algorithm and the actual ship experiment results of manual ship maneuvering, it is shown that the method can effectively avoid collisions based on safe encounter distances that comply with navigation experience in different encounter situations. At the same time, it has better performance in collision avoidance behavior. It has certain feasibility and practical applicability.

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Spatial patterns of light response parameters and their regulation on gross primary productivity in China - Yong Lin; Zhi Chen; Guirui Yu; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Wenxing Luo (Agricultural and Forest Meteorology, 2024)

Re-evaluating the impact and mechanism of digital economy on regional pollution intensity from the perspective of spatial spillover - Pei-Ling Yang; Zi-Han Lin; Zhen-Ning Zhu; Feng-Wei Ying (Environmental Science and Pollution Research, 2024)

Fabrication and performance of novel multifunctional sodium alginate/polyvinylpyrrolidone hydrogels - Deli Lu; Chen Liu; Fengtian Zhu; Ying Liu; Yushi Lin; Qidong Yang; Sheng Han (Chemosphere, 2024)

Hydrological connectivity controls on the dynamics of particulate organic matter in a semi-enclosed mariculture bay - Aiqin Han; Jin-Yu Terence Yang; Mengli Chen; Zhenzhen Zheng; Xijie Yin; Hui Lin; Min Nina Xu; Shuh-Ji Kao (Aquaculture, 2024)

Review of risk assessment for navigational safety and supported decisions in arctic waters - X. Yang; Z.Y. Lin; W.J. Zhang; S. Xu; M.Y. Zhang; Z.D. Wu; B. Han (Ocean & Coastal Management, 2024)

Warming effects on C:N:P stoichiometry and nutrient limitation in terrestrial ecosystems - Hongwei Xu; Minggang Wang; Chengming You; Bo Tan; Lin Xu; Han Li; Li Zhang; Lixia Wang; Sining Liu; Guirong Hou; Yang Liu; Zhenfeng Xu; et al. (Soil and Tillage Research, 2024)

Adding Corbicula fluminea altered the effect of plant species diversity on greenhouse gas emissions and nitrogen removal from constructed wetlands in the low-temperature season - Luping Yang; Kai Shen; Xile Xu; Derong Xiao; Huijuan Cao; Yishi Lin; Xiangyong Zheng; Min Zhao; Wenjuan Han (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

High-performance petal-like nickel organic framework for efficient dye sequestration - Frank Peprah Addai; Yuelin Liu; Jiacong Wu; Xinnan Ma; Juan Han; Feng Lin; Fengcheng Xue; Yang Zhou; Yun Wang (Journal of Water Process Engineering, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Eupatilin inhibits xanthine oxidase in vitro and attenuates hyperuricemia and renal injury in vivo - Guitao Xu; Lele Wu; Hongxuan Yang; Tianfeng Liu; Ying Tong; Jiliang Wan; Bin Han; Lin Zhou; Xuguang Hu (Food and Chemical Toxicology, 2024)

Boosting decarboxylation of monomethyl adipate coupling to dimethyl sebacate through Pt electrode at high current density - Linchuan Cong; Yupeng Wu; Nan Lin; Xinxin Li; Fangbing Liu; Fuyu Han; Jin Yang; Ciduo Wang; Haibo Lin (Chemical Engineering Journal, 2024)

Organic hybrid tetranuclear clusteroluminogens: Blue-light-excitable LED with ultrahigh luminous efficacy - Yang-Peng Lin; Xuexia Lu; Zhizhuan Zhang; Xinghui Qi; Jiance Jin; Jielong Xu; Yancong Wu; Yanan Wu; Zhonghua Deng; Xiao-Ying Huang; Cuiping Han; Sanlue Hu; et al. (Chemical Engineering Journal, 2024)

PCAP-1a, an exopolysaccharide from Pectobacterium actinidiae, exerts the dual role of immunogenicity and virulence in plants - Zhixiang Yuan; Tingmi Yang; Qingping Xiong; Yuqi Shi; Xixi Han; Yuqing Lin; Njoroge Hellen Wambui; Zhuang Liu; Yunpeng Wang; Hongxia Liu (Carbohydrate Polymers, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Study on ecological compensation quotas in different confined areas of coastal zone - A case study of mangrove reserve in shankou, guangxi, China - Xin Nie; Lin He; Zhoupeng Chen; Mengshi Yang; Yuanyuan Li; Xiaowei He; Han Wang; Wei Gao (Ocean & Coastal Management, 2023)

Distribution and abundance of oil-degrading bacteria in seawater of the Yellow Sea and Bohai Sea, China - Haolei Shi; Wei Gao; Yunchao Zheng; Lin Yang; Bin Han; Yanchao Zhang; Li Zheng (Science of The Total Environment, 2023)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Decoding the marine biogeochemical cycling of mercury by stable mercury isotopes - Lin Yang; Ben Yu; Deming Han; Kun Zhang; Hongwei Liu; Cailing Xiao; Ligang Hu; Yongguang Yin; Jianbo Shi; Guibin Jiang (Critical Reviews in Environmental Science and Technology, 2023)

Disentangling the relative importance of precipitation, biocrust succession, and shrub cover in mediating soil phoD-harbouring communities and organic phosphorus mineralisation - Lin Xu; Xiangzhen Li; Chaonan Li; Yongping Kou; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; Sining Liu; et al. (Soil Biology and Biochemistry, 2023)

Fault diagnosis of regenerative thermal oxidizer system via dynamic uncertain causality graph integrated with early anomaly detection - Shangbo Han; Yiyan Hua; Yangshu Lin; Longchao Yao; Zhongcheng Wang; ZhengJie Zheng; Jian Yang; Chunhui Zhao; Chenghang Zheng; Xiang Gao (Process Safety and Environmental Protection, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Techno-economic comparison on charging modes of battery heavy-duty vehicles in short-haul delivery: A case study of China - Zhichao Wang; Yang Liu; Zhenhong Lin; Han Hao; Shunxi Li (Journal of Cleaner Production, 2023)

Unlocking the potential of elemental sulfur autotrophic denitrification through inorganic nutrient optimization - Yi-Lu Sun; Xue-Ning Zhang; Han-Lin Wang; Chen-Yang Shao; Wei-Qin Zhuang; Hao-Yi Cheng; Ji-Xian Yang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Design of rich defects carbon coated MnFe2O4/LaMnO3/LaFeO3 heterostructure nanocomposites for broadband electromagnetic wave absorption - Xinyang Liu; Lin He; Guanghui Han; Jie Sheng; Yongsheng Yu; Weiwei Yang (Chemical Engineering Journal, 2023)

Optimizing inorganic carbon and salinity for enhanced biomass and pigment production in Colaconema formosanum: Implications for sustainable carbon sequestration and stress responses - Han-Yang Yeh; Wei-Lung Wang; Yung-Kai Lin; Fan-Hua Nan; Meng-Chou Lee (Bioresource Technology, 2023)

Nonparametric estimation for planetary soil based on numerical simulation of penetration process - Han Huang; Xintao Yang; Shucai Xu; Lin Yang; Haozhe Wang; Zhixin Xiang; Qinghao Yan (Advances in Space Research, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Acetylcholine (ACh) enhances Cd tolerance through transporting ACh in vesicles and modifying Cd absorption in duckweed (Lemna turionifera 5511) - Lin Yang; Xu Ma; Yuhan Guo; Yuman He; Yunwen Yang; Wenqiao Wang; Ziyi Xu; Zhaojiang Zuo; Ying Xue; Rui Yang; Bing Han; Jinsheng Sun (Environmental Pollution, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Behaviour of recycled aggregate concrete-filled stainless steel tubular columns subjected to lateral monotonic and cyclic loading - Chuan-Yang Xu; Lin-Hai Han; Chao Hou (Engineering Structures, 2023)

Removal of antibiotic-resistant bacteria and genes by Solar-activated Ferrate/ Peroxymonosulfate: Efficiency in aquaculture wastewater and mechanism - Ruixue Li; Xudai Wu; Zhenfei Han; Lijie Xu; Lu Gan; Yanqiong Zhang; Fengru Lu; Hua Lin; Xue Yang; Muting Yan; Wei Chu; Han Gong (Chemical Engineering Journal, 2023)

Conditioned medium of human menstrual blood-derived endometrial stem cells protects against cell inflammation and apoptosis of Npc1KO N2a cells - Minlin Yang; Yanchun Zhao; Xiaoying Li; Han Li; Fangfang Cheng; Yanli Liu; Zisen Jia; Ya’nan He; Juntang Lin; Lihong Guan (Metabolic Brain Disease, 2023)

Degradation of indole via a two-component indole oxygenase system from Enterococcus hirae GDIAS-5 - Jun-Jin Deng; Jing-Yi Hu; Xue-ying Han; Yang Li; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li (Journal of Hazardous Materials, 2023)

Deep removal of fluoride from tungsten smelting wastewater by combined chemical coagulation-electrocoagulation treatment: From laboratory test to pilot test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Meirong Wu; Lei Yang; Huanjun Bao; Jianhua Kang; Haisheng Han; Chenyang Zhang; Wei Sun (Journal of Cleaner Production, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

Marine fungus-derived alkaloid inhibits the growth and metastasis of gastric cancer via targeting mTORC1 signaling pathway - Shuai Ma; Yiwei Hu; Jianjiao Chen; Xiaojuan Wang; Chenxi Zhang; Qianqian Liu; Guodi Cai; Hong Wang; Jianwei Zheng; Qianqian Wang; Lin Zhong; Bin Yang; et al. (Chemico-Biological Interactions, 2023)

Capsular polysaccharide mediates Streptococcus agalactiae to resist Nile tilapia macrophage phagocytosis - Yanjian Yang; Meng Chen; Zhelin Wu; Defeng Zhang; Huiyan Lin; Xiayi Wei; Biao Han; Zheng Guo; Jianmin Ye (Aquaculture, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Huanjun Bao; Meirong Wu; Lei Yang; Gaogui Jing; Haisheng Han; Chenyang Zhang; Xiaoyun Jiang; Songlin Wang; Wei Ding; et al. (Journal of Environmental Management, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Strategies for controlling gas evolution reactions to boost the divergent paired electrochemical upgrading of furfural in acidic environment - Xinxin Li; Linchuan Cong; Yupeng Wu; Nan Lin; Fangbing Liu; Deyuan Xin; Fuyu Han; Jin Yang; Weitong Chen; Haibo Lin (Chemical Engineering Journal, 2023)

Excitation- & concentration-dependent color-tunable ultra-long phosphorescence of isophthalonitriles doped polymers - Xiaoxin Zheng; Jinke Jiang; Qinglian Lin; Cuicui Li; Jiashuai Chen; Shuwen Wang; Quanxiang Han; Xin Ye; Yang Liu; Xutang Tao (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Short-term Dietary Selenium Deficiency Induced Liver Fibrosis by Inhibiting the Akt/mTOR Signaling Pathway in Rats - Lichun Qiao; Xue Lin; Yan Zhao; Qingfeng Wang; Haobiao Liu; Mei You; Qian Yuan; Zhihao Yang; Wenming Bian; Jiaxin Liu; Ziwei Guo; Jing Han (Biological Trace Element Research, 2023)

A New Method for Converting T2 Spectrum into Pore Radius - Fan Zhang; Zhenxue Jiang; Yuanhao Zhang; Bin Hu; Zaiquan Yang; Yuhua Yang; Xianglu Tang; Hanmin Xiao; Lin Zhu; Yunhao Han (Journal of Earth Science, 2023)

Assessment of various conditions for the simultaneous determination of US EPA and EU priority PAHs in coffee samples and their PAHs consumption risk - Yu-Fang Huang; Po-Lin Liao; Yi-Jun Lin; Shih-Han Huang; Yi-Hsieng Samuel Wu; Chia-Fang Teng; Deng-Jye Yang (Food Research International, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

An accurate and efficient method for simultaneous determination of 16 trichothecenes in maize and wheat by UHPLC-Q-Orbitrap-HRMS combined one-step pretreatment with a novel isotope multipoint calibration strategy - Yu Wu; Jin Ye; Songshan Wang; Xiaomin Han; Li Li; Lin Zhu; Sen Li; Hongmei Liu; Yang Wang; Yi Shao; Songxue Wang (Food Control, 2023)

Combined exposure to lead and high-fat diet induced neuronal deficits in rats: Anti-neuroinflammatory role of SIRT1 - Mengchen Liu; Rundong Liu; Mingzhi Yang; Yue Ba; Qihong Deng; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (Food and Chemical Toxicology, 2023)

Mixed exposure effect of seminal metals on semen quality, mediation of total antioxidant capacity, and moderation of GSTM1/GSTT1 gene deletion in Chinese reproductive-aged men - Jingchao Ren; Huidong Jin; Chen Zhang; Song Liu; Yufen Han; Jinyan Xi; Jinhu Cao; Fenglong Lin; Pingyang Zhang; Fengquan Zhang; Guang-hui Zhang; Huijun Yang; et al. (Environmental Research, 2023)

Identification and protective role of CD34+ stromal cells/telocytes in experimental autoimmune encephalomyelitis (EAE) mouse spleen - Ganesh Dama; Xiaoxi Hu; Yushan Yan; Yonghai Li; Han Li; Fen Yang; Yanli Liu; Juntang Lin (Histochemistry and Cell Biology, 2023)

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

Magnetotelluric constraints on the tectonic evolution beneath the Luotian dome in the North Dabie complex zone, Central China - Bo Yang; Yufeng Chen; Bo Han; Wule Lin; Xiangyun Hu; Jian Lin (Tectonophysics, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Arsenic triggered nano-sized uranyl arsenate precipitation on the surface of Kocuria rosea - Lei Zhou; Faqin Dong; Xiangyu Xi; Lin Zhou; Qunwei Dai; Mingxue Liu; Ying Han; Gang Yang; Yongde Zhang (Journal of Environmental Radioactivity, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

Response mechanisms of Chlorella sorokiniana to microplastics and PFOA stress: Photosynthesis, oxidative stress, extracellular polymeric substances and antioxidant system - Zhilin Zhao; Xiaoying Zheng; Zongshuo Han; Shanshan Yang; Huijie Zhang; Tao Lin; Chao Zhou (Chemosphere, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Substantial short- and long-term health effect due to PM2.5 and the constituents even under future emission reductions in China - Shengnan Xiang; Xiuwen Guo; Wenbin Kou; Xinran Zeng; Feifan Yan; Guangliang Liu; Yuanyuan Zhu; Yang Xie; Xiaopei Lin; Wei Han; Yang Gao (Science of The Total Environment, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Upcycling of nickel iron slags to hierarchical self-assembled flower-like photocatalysts for highly efficient degradation of high-concentration tetracycline - Zhen Wu; Mengye Wang; Yang Bai; Han Song; Jiaxin Lv; Xiaofeng Mo; Xiaoqin Li; Zhang Lin (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Morphological and physicochemical characteristics, biological functions, and biomedical applications of diatom frustule - Chenfei Yang; Chao Feng; Yuhang Li; Zheng Cao; Yan Sun; Xiaohui Li; Lin Zhang; Chengxu Zhou; Jichang Han (Algal Research, 2023)

Effect of nicosulfuron on dynamic changes in the starch-sugar interconversion in sweet maize (Zea mays L.) - Jian Wang; Qing Yang; Jinling Han; Zidian He; Min Yang; Xiuping Wang; Xiaohu Lin (Environmental Science and Pollution Research, 2023)

Donor-acceptor engineered g-C3N4 enabling peroxymonosulfate photocatalytic conversion to 1O2 with nearly 100% selectivity - Zonglin Weng; Yuanfang Lin; Bin Han; Xinfei Zhang; Qin Guo; Yu Luo; Xinwen Ou; Yang Zhou; Jin Jiang (Journal of Hazardous Materials, 2023)

Rational design of donor-acceptor engineered g-C3N4 for boosted H2O2 production via photocatalytic O2 reduction - Yu Luo; Yuanfang Lin; Zonglin Weng; Bin Han; Yang Zhou; Xinwen Ou; Jin Jiang (Journal of Environmental Chemical Engineering, 2023)

Soil bacteria respond intensely to resource limitations regulated by edaphic properties during secondary succession on a semiarid abandoned farmland - Zekun Zhong; Xing Wang; Rentao Liu; Dejie Kong; Haojie Nie; Xinhui Han; Gaihe Yang; Lin Zhu (CATENA, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Two Novel Species of Mesophoma gen. nov. from China - Ai-Ling Yang; Lin Chen; Lu Cheng; Jin-Peng Li; Zhao-Ying Zeng; Han-Bo Zhang (Current Microbiology, 2023)

m6A writer WTAP targets NRF2 to accelerate bladder cancer malignancy via m6A-dependent ferroptosis regulation - Ke Wang; Gang Wang; Gang Li; Wei Zhang; Yarong Wang; Xiaofeng Lin; Chengxian Han; Hanxuan Chen; Liang Shi; Abudoula Reheman; Jingkai Li; Zhaomin Li; et al. (Apoptosis, 2023)

Platycodon grandiflorus subjected to full- and restricted-water regimes show differential biosynthesis of triterpenoid saponins - Min Li; Lin Cheng; Meng Zhang; Li Min Yang; Mei Han (Acta Physiologiae Plantarum, 2023)

A case of A133V genetic Creutzfeldt–Jakob disease presenting with bilateral thalamic lesions and atypical clinical features - Shi-Lin Yang; Shu-Fen Chen; Chong-Bo Zhao; Xiang Han (Acta Neurologica Belgica, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

Reversal of soil moisture constraint on vegetation growth in North China - Ruohua Du; Jianjun Wu; Feng Tian; Jianhua Yang; Xinyi Han; Meng Chen; Bingyu Zhao; Jingyu Lin (Science of The Total Environment, 2023)

Swallowtail butterflies and hawkmoths contribute equally to the pollination of Habenaria dentata (Orchidaceae) - Shao-Lin Tan; Xing-Hui Chen; Hai-Hong Liao; Lang Huang; Han-Wen Xiao; Huo-Lin Luo; Dong-Jin Xiong; Bo-Yun Yang; Zong-Xin Ren (Flora, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Development of mitochondrial simple sequence repeat markers to simultaneously distinguish cytoplasmic male sterile sources in cotton - Yongqi Li; Meng Zhang; Kashif Shahzad; Yang Han; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Hailin Wang; Xiuqin Qiao; Juanjuan Feng; Zhongxu Lin; et al. (Functional & Integrative Genomics, 2023)

A Data-Driven Intelligent Prediction Approach for Collision Responses of Honeycomb Reinforced Pipe Pile of the Offshore Platform - Lei Yang; Hong Lin; Chang Han; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2023)
The potential collision between the ship and the pipe piles of the jacket structure brings huge risks to the safety of an offshore platform. Due to their high energy-absorbing capacity, honeycomb structures have been widely used as impact protectors in various engineering applications. This paper proposes a data-driven intelligent approach for the prediction of the collision response of honeycomb-reinforced structures under ship collision. In the proposed model, the artificial neural network (ANN) is combined with the dynamic particle swarm optimization (DPSO) algorithm to predict the collision responses of honeycomb reinforced pipe piles, including the maximum collision depth (δmax) and maximum absorption energy (Emax). Furthermore, a data-driven evaluation method, known as grey relational analysis (GRA), is proposed to evaluate the collision responses of the honeycomb-reinforced pipe piles of offshore platforms. Results of the case study demonstrate the accuracy of the DPSO-BP-ANN model, with measured mean-square-error (MSE) of 5.06 × 10−4 and 4.35 × 10−3 and R2 of 0.9906 and 0.9963 for δmax and Emax, respectively. It is shown that the GRA method can provide a comprehensive evaluation of the performance of a honeycomb structure under impact loads. The proposed model provides a robust and efficient assessment tool for the safe design of offshore platforms under ship collisions.

The effect of short-term air pollutants exposure on outpatient admission for blepharitis in Shanghai, China: a hospital-based study - Han Zhao; Tong Lin; Yun Yang; Changming Feng; Wushuang Wang; Lan Gong (Environmental Science and Pollution Research, 2023)

Tolerance and recovery of aerobic granular sludge: Impact of perfluorooctanoic acid - Xiaoying Zheng; Huijie Zhang; Zhi Xu; Tao Lin; Shanshan Yang; Zhilin Zhao; Zongshuo Han; Chao Zhou (Chemosphere, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

Urban park use and self-reported physical, mental, and social health during the COVID-19 pandemic: An on-site survey in Beijing, China - Di Lin; Yan Sun; Yue Yang; Yi Han; Chengyang Xu (Urban Forestry & Urban Greening, 2023)

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Reaction gas-induced partial exsolution of Pd from PdCeMnO for methane combustion - Han Zhao; Yuanlong Tan; Lin Li; Yang Su; Aiqin Wang; Xiao Yan Liu; Tao Zhang (Chemical Engineering Journal, 2023)

Clustered regularly interspaced short palindromic repeats (CRISPR) technology and genetic engineering strategies for microalgae towards carbon neutrality: A critical review - Tse-Min Lee; Jia-Yi Lin; Tsung-Han Tsai; Ru-Yin Yang; I-Son Ng (Bioresource Technology, 2023)

Biodynamic responses of adolescent idiopathic scoliosis exposed to vibration - Shaowei Jia; Liying Lin; Hufei Yang; Junde Xie; Zefeng Liu; Tianyou Zhang; Jie Fan; Li Han (Medical & Biological Engineering & Computing, 2023)

Control measure implications of COVID-19 infection in healthcare facilities reconsidered from human physiological and engineering aspects - Ying-Fei Yang; Yi-Jun Lin; Shu-Han You; Tien-Hsuan Lu; Chi-Yun Chen; Wei-Min Wang; Chung-Min Liao (Environmental Science and Pollution Research, 2022)

Numerical Investigation on Performance Optimization of Offshore Sandwich Blast Walls with Different Honeycomb Cores Subjected to Blast Loading - Hong Lin; Chang Han; Lei Yang; Lin Zhang; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
As an important protective facility on offshore platform, the blast wall is of great significance in resisting oil and gas explosions. Honeycomb structures are widely used due to their unique deformation and mechanical properties under dynamic impact loads. The aim of this research is to develop an optimized design for an offshore sandwich blast wall with different honeycomb cores. The uniqueness of this paper is providing the quantitative optimization scheme for topological configurations and unit cell geometric parameters of honeycomb structures according to mass consistency and the proposed synthetic evaluation index of anti-blast performance. By using the numerical simulation software ANSYS/LS-DYNA, the CONWEP algorithm was first validated and then adopted to conduct the dynamical performance analysis of the honeycomb blast wall. For comparison purposes, simulating studies on a series of different blast walls were carried out by considering various influential parameters. According to different criteria, the blast resistance of the sandwich honeycomb structures was evaluated. It is found that the sandwich plate with concave arc honeycomb core has the best anti-blast performance compared to that of arrow honeycomb core and concave hexagonal honeycomb core. For the concave arc honeycomb structure, the geometric parameters such as concave angle and aspect ratio of honeycomb unit cell have great influence on the blast-resistance performance. Moreover, the concave arc honeycomb structure with positive gradient arrangement has better anti-blast performance than the negative one. The curved blast wall with the curvature of 1/20 achieves better anti-blast performance than the flat blast wall.

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Optimized thyroid transcription factor-1 core promoter-driven microRNA-7 expression effectively inhibits the growth of human non-small-cell lung cancer cells - Shipeng Chen; Lian Guan; Xu Zhao; Jing Yang; Longqing Chen; Mengmeng Guo; Juanjuan Zhao; Chao Chen; Ya Zhou; Yong Han; Lin Xu (Journal of Zhejiang University-SCIENCE B, 2022)

PDGFD switches on stem cell endothelial commitment - Weisi Lu; Peipei Xu; Boxiong Deng; Jianing Zhang; Ying Zhan; Xianchai Lin; Xiangzhong Xu; Zhaoxia Xia; Xiaoxi Yang; Xiaoling Zeng; Lijuan Huang; Bingbing Xie; et al. (Angiogenesis, 2022)
The critical factors regulating stem cell endothelial commitment and renewal remain not well understood. Here, using loss- and gain-of-function assays together with bioinformatic analysis and multiple model systems, we show that PDGFD is an essential factor that switches on endothelial commitment of embryonic stem cells (ESCs). PDGFD genetic deletion or knockdown inhibits ESC differentiation into EC lineage and increases ESC self-renewal, and PDGFD overexpression activates ESC differentiation towards ECs. RNA sequencing reveals a critical requirement of PDGFD for the expression of vascular-differentiation related genes in ESCs. Importantly, PDGFD genetic deletion or knockdown increases ESC self-renewal and decreases blood vessel densities in both embryonic and neonatal mice and in teratomas. Mechanistically, we reveal that PDGFD fulfills this function via the MAPK/ERK pathway. Our findings provide new insight of PDGFD as a novel regulator of ESC fate determination, and suggest therapeutic implications of modulating PDGFD activity in stem cell therapy.

Transcriptome and metabolome profiling of interspecific CSSLs reveals general and specific mechanisms of drought resistance in cotton - Bei Han; Fengjiao Wang; Zhilin Liu; Lin Chen; Dandan Yue; Weinan Sun; Zhongxu Lin; Xianlong Zhang; Xiaofeng Zhou; Xiyan Yang (Theoretical and Applied Genetics, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Progress of Selenium Deficiency in the Pathogenesis of Arthropathies and Selenium Supplement for Their Treatment - Huan Deng; Haobiao Liu; Zhihao Yang; Miaoye Bao; Xue Lin; Jing Han; Chengjuan Qu (Biological Trace Element Research, 2022)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

Three-dimensional characteristics of mesoscale eddies simulated by a regional model in the northwestern Pacific Ocean during 2000–2008 - Guijing Yang; Xiayan Lin; Guoqing Han; Yu Liu; Gengxin Chen; Jianhui Wang (Acta Oceanologica Sinica, 2022)

The differential impact of air pollutants on acute urticaria and chronic urticaria: a time series analysis - Jiawei Li; Guoqiang Song; Zhenzhen Mu; Xiaoou Lan; Fan Yang; Lin Li; Xiuping Han (Environmental Science and Pollution Research, 2022)

Spatio-temporal analysis of east greenland polar front - Yu Liu; Jianhui Wang; Guoqing Han; Xiayan Lin; Guijing Yang; Qiyan Ji (Frontiers in Marine Science, 2022)
The East Greenland Polar Front (EGPF) is an important front with strong salinity and temperature gradients in the Nordic Seas. It is formed by the interaction between Arctic-origin and Atlantic-origin water. The variations of EGPF are closely linked with sea ice melting and heat content transport associated with North Atlantic water recirculation. For a three-dimensional (3D) daily analysis, we use the global ocean eddy resolution reanalysis product (GLORYS12V1) from 1993 to 2018 to calculate the salinity and temperature horizontal gradient in the upper ocean and obtain the spatiotemporal distribution and intensity characteristics of EGPF. After assessment, the thresholds of the salinity and temperature fronts are set to 0.04 psu/km and 0.09°C/km, respectively. Compared with satellite observations of sea ice concentration, a significant spatial relationship is observed between the main position of EGPF and the ice edge before the sea ice shrinks to the continental shelf sea area. Affected by the freshening of the Arctic-origin water due to the melting of the sea ice, the intensity and area of EGPF show significant seasonal variations. Against the background of global warming, the sea ice area presents an obvious decreasing trend in the Greenland Sea. The melting of sea ice increased annually every summer from 1998 to 2018. The heat content transport of the Atlantic-origin water has also increased in recent years. The 3D characteristics (intensity and volume) of EGPF as salinity and temperature fronts exhibit increasing trends.

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Dynamic Performance and Crashworthiness Assessment of Honeycomb Reinforced Tubular Pipe in the Jacket Platform under Ship Collision - Hong Lin; Chang Han; Lei Yang; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
The collision between the pipe legs of jacket platforms and bypassing ships is of great concern for the safety assessment of platforms. Honeycomb structures have been widely used owing to their unique deformation and mechanical properties under dynamic impact loads. In this paper, two typical honeycomb structures, namely hexagonal honeycomb and arrow honeycomb, were constructed for the impact protection of inclined pipe legs in jacket platforms, and the present study aimed to assess the dynamical performance and crushing resistance of the designed honeycomb reinforced structure under ship collision by using the numerical simulation software ANSYS/LS-DYNA. The dynamical performance of the honeycomb reinforced pipe leg was investigated considering various influential parameters, including the impact velocity and impact direction. The crashworthiness of the two types of honeycomb was evaluated and compared by different criteria, namely the maximum impact depth (δmax), specific energy absorption (SEA) and the proposed index offset sliding (OS). The results demonstrated that both the hexagonal honeycomb structure and the arrow honeycomb structure can reduce the damage of inclined pipe legs caused by ship collision, while the hexagonal honeycomb can provide the better anti-collision capacity, which can well reduce the offset sliding and better protect the pipe leg from ship collision.

Chromosomal mapping of a locus associated with adult-stage resistance to powdery mildew from Agropyron cristatum chromosome 6PL in wheat - Yida Lin; Shenghui Zhou; Xuezhong Liang; Baojin Guo; Bing Han; Haiming Han; Jingpeng Zhang; Yuqing Lu; Zhi Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; et al. (Theoretical and Applied Genetics, 2022)

Biomechanical Analysis of Mandibular Implant-Assisted Removable Partial Denture with Distal Extension - Yung-Chung Chen; Chi-Lun Lin; Chen-Han Yu; Hung-Chih Chang; Yang-Ming Lin; Jia-Wei Lin (Journal of Medical and Biological Engineering, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Evaluation of PET List Data-Driven Gated Motion Correction Technique Applied in Lung Tumors - Yi-Lun Chen; Bang-Hung Yang; I.-Ling Shih; Ko-Han Lin (Journal of Medical and Biological Engineering, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Functional connections between bird eggshell stiffness and nest characteristics through risk of egg collision in nests - Chih‐Ming Hung; Shu‐Han Tsao; Pei‐Lin Chiang; Shang‐Ping Wu; Mao‐Ning Tuanmu; Jia‐Yang Juang (Ecology Letters, 2022)
Eggs and nests are two critical traits for the ecological success of birds. Their functional interactions, however, remain unclear. Here, we examined the functional connections between egg stiffness and nest attachment, site and structure for 1350 avian species. We revealed high eggshell stiffness for eggs in nests with a pensile attachment, located on non‐tree vegetation or having a domed shape, suggesting that birds produce stiffer eggs in response to higher egg‐collision risk in unstable or enclosed nests. Interdependence models suggested that the evolution of eggshell stiffness was more likely to be driven by than drive that of nest characters. Our results implied a trade‐off between investment in competing for established nesting niches and producing stiff eggs to explore novel niches with high collision risk, possibly mediated by predation or thermoregulation. This study highlights an overlooked connection between nests and eggshells that may have broadened the ecological niches of birds.

An implementation framework of blockchain-based hazardous waste transfer management system - Guanghan Song; Yujie Lu; Haibo Feng; Han Lin; Yang Zheng (Environmental Science and Pollution Research, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

Characteristic Strength and Energy Evolution Law of Coal Treated by Ultrasonic Wave with Different Power Under Uniaxial Compression - Erhao Yang; Haifei Lin; Shugang Li; Pengxiang Zhao; Lei Qin; Ruizhe Wang; Shuangze Han (Natural Resources Research, 2022)

The significance of riparian communities in the energy flow of subtropical stream ecosystems - Yi-Chang Liao; An-Cheng Lin; Han-Ni Tsai; Yu-Ting Yen; Chyng-Shyan Tzeng; Man-Miao Yang; Hsing-Juh Lin (Aquatic Sciences, 2022)

Towards a rapid assessment of highway slope disasters by using multidisciplinary techniques - Meng-Chia Weng; Cheng-Han Lin; Wen-Jie Shiu; Wei-An Chao; Chia-Chi Chiu; Ching-Fang Lee; Wei-Kai Huang; Che-Ming Yang (Landslides, 2022)
Mega-earthquakes and extreme climate events accompanied by intrinsic fragile geology lead to numerous landslides along mountain highways in Taiwan, causing enormous life and economic losses. In this study, a system for rapid slope disaster information integration and assessment is proposed with the aim of providing information on landslide occurrence, failure mechanisms, and subsequent landslide-affected areas to the highway authority rapidly. The functionality of the proposed system is deployed into three units: (1) geohazard rapid report (GeoPORT I), (2) multidisciplinary geological survey report (GeoPORT II), and (3) site-specific landslide simulation report (GeoPORT III). After landslide occurrence, the seismology-based monitoring network rapidly provides the initial slope disaster information, including preliminary location, event magnitude, earthquake activity, and source dynamics, within an hour. Within 3 days of the landslide, a multidisciplinary geological survey is conducted to collect high-precision topographical, geological, and remote-sensing data to determine the possible failure mechanism. After integrating the aforementioned information, a full-scale three-dimensional landslide simulation based on the discrete element method is performed within 10 days to reveal the failure process and to identify the areas potentially affected by subsequent disasters through scenario modeling. Overall, the proposed system can promptly provide comprehensive and objective information to relevant authorities after the event occurrence for hazard assessment. The proposed system was validated using a landslide event in the Central Cross-Island Highway of Taiwan.

Distributions, origins, and health-risk assessment of nitrate in groundwater in typical alluvial-pluvial fans, North China Plain - Lin Gan; Guanxing Huang; Lixin Pei; Yanjing Gan; Chunyan Liu; Mingnan Yang; Dongya Han; Jiangmin Song (Environmental Science and Pollution Research, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

CRISPR-Cas9-Mediated Gene Therapy in Neurological Disorders - Lihong Guan; Yawei Han; Ciqing Yang; Suxiang Lu; Jiang Du; Han Li; Juntang Lin (Molecular Neurobiology, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Master regulator NtrC controls the utilization of alternative nitrogen sources in Pseudomonas stutzeri A1501 - Zhimin Yang; Qin Li; Yongliang Yan; Xiubin Ke; Yueyue Han; Shaoyu Wu; Fanyang Lv; Yahui Shao; Shanshan Jiang; Min Lin; Yunhua Zhang; Yuhua Zhan (World Journal of Microbiology and Biotechnology, 2021)
Pseudomonas stutzeri A1501 is a model strain used to study associative nitrogen fixation, and it possesses the nitrogen regulatory NtrC protein in the core genome. Nitrogen sources represent one of the important factors affecting the efficiency of biological nitrogen fixation in the natural environment. However, the regulation of NtrC during nitrogen metabolism in P. stutzeri A1501 has not been clarified. In this work, a phenotypic analysis of the ntrC mutant characterized the roles of NtrC in nitrogen metabolism and the oxidative stress response of P. stutzeri A1501. To systematically identify NtrC-controlled gene expression, RNA-seq was performed to further analyse the gene expression differences between the wild-type strain and the ∆ ntrC mutant under nitrogen fixation conditions. A total of 1431 genes were found to be significantly altered by ntrC deletion, among which 147 associative genes had NtrC-binding sites, and the pathways for nitrogen fixation regulation, nitrogenous compound acquisition and catabolism and nitrate assimilation were discussed. Furthermore, the oxidative stress-related gene ( katB ), which was upregulated by ntrC deletion, was suggested to be a potential target gene of NtrC, thus highlighting the importance of NtrC in nitrogenase protection against oxygen damage. Based on these findings, we propose that NtrC is a high-ranking element in the regulatory network of P. stutzeri A1501 that controls a variety of nitrogen metabolic and oxidative stress responsive traits required for adaptation to complex rhizosphere environments.

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Stenotrophomonas strain CPCC 101271, an intestinal lifespan-prolonging bacterium for Caenorhabditis elegans that assists in host resistance to “Bacillus nematocida” colonization - Rui Han; Yu Wang; Yang Deng; Yuqin Zhang; Lin Zhang; Qiuhong Niu (Archives of Microbiology, 2021)
The soil-dwelling, opportunistic pathogenic bacterium "Bacillus nematocida" B16 exhibits strong killing activities against a variety of pathogenic nematodes via a “Trojan horse” mechanism that can kill worm species like Caenorhabditis elegans . The bacterial strain CPCC 101271 was previously isolated from the intestines of C. elegans that were recovered from natural habitats and can serve as a probiotic for C. elegans , while also assisting in resistance to infection by the pathogenic strain B16. In this study, the lifespan of C. elegans fed with strain CPCC 101271 cells was extended by approximately 40% compared with that of worms fed with Escherichia coli OP50 cells. In addition, the colonization of C. elegans by the pathogenic bacterium "B. nematocida" B16 was inhibited when pre-fed with strain CPCC 101271. Metagenomic sequence analysis of intestinal microbiota of C. elegans fed with strain CPCC 101271 and infected with B16 revealed that pre-feeding worms with CPCC 101271 improved the diversity of the intestinal bacteria. Moreover, community structure significantly varied in coordination with Stenotrophomonas spp. and Bacillus spp. abundances when competition between strains CPCC 101271 and B16 was evaluated. In conclusion, the nematode microbiota strain CPCC 101271 assisted in its host resistance to colonization by the pathogen "Bacillus nematocida" and can also promote life span-prolongation in C. elegans. These results underscore that understanding the interactions between C. elegans microbiota and pathogens can provide new insights into achieving effective biological control of agricultural pests.

Integration of small RNAs, degradome, and transcriptome sequencing provides insights into the differences between Shizhu ginseng and Yuan ginseng - Mengyuan Peng; Yanlin Chen; Wenjuan Wang; Zhihua He; Wangqiang Dai; Zhiyun Lin; Zemin Yang; Mengjuan Gong; Yongqin Yin; Bin Han; Yu Zeng; Yingfang Wang (Journal of Plant Biochemistry and Biotechnology, 2021)
Panax ginseng is one of the most popular herbs which have been used as an important traditional Chinese medicine since ancient times. Yuan ginseng and Shizhu ginseng,which belong to P. ginseng , are widely used as substitutes for wild ginseng in clinical practice. Clinical practice has proved that the clinical efficacy of Shizhu ginseng is better than Yuan ginseng. However, current research cannot completely explain this phenomenon. Considering that small RNA may be one of the pharmacodynamic substances of P. ginseng , it is challenging to investigate differential miRNAs between Shizhu ginseng and Yuan ginseng. In this study, the transcriptome, small RNAome and degradome of P. ginseng were studied by high-throughput sequencing. A total of 63,875 unigenes and 43,950,137 small RNA clean reads were obtained from the roots of P. ginseng . Among 3206 differentially expressed genes, 1190 genes were up-regulated in Yuan ginseng when compared with Shizhu ginseng. 24 known differential miRNAs and 7 novel differential miRNAs were obtained. The 304 targets of 24 differentially expressed miRNA (17 known and 7 novel) families are mainly related to energy metabolism, biotic stress and disease immunity in ginseng itself. Through the association analysis of mRNA and miRNA, our work gives a better understanding of the difference between Yuan ginseng and Shizhu ginseng. Considering the cross-kingdom regulation of plant miRNAs, our results may provide a foundation for understanding the miRNA-dependent clinical efficacy in P. ginseng .

Nanotechnology advances in pathogen- and host-targeted antiviral delivery: multipronged therapeutic intervention for pandemic control - Kai-Chieh Yang; Jung-Chen Lin; Hsiao-Han Tsai; Chung-Yao Hsu; Vicky Shih; Che-Ming Jack Hu (Drug Delivery and Translational Research, 2021)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Disrupted white matter functional connectivity in aMCI APOEε4 carriers: a resting-state study - Hua Lin; Muwei Li; Yang Zhan; Li Lin; Kun Yang; Shimin Hu; Ying Han (Brain Imaging and Behavior, 2021)

Mild encephalitis/encephalopathy with a reversible splenial lesion associated with respiratory syncytial virus infection in infants - Xue-Lin Li; Jinming Han; Zhong-Rui Yan; Bing-Wei Zhang; Hai-Yang Wang (Journal of NeuroVirology, 2021)

Quantitative Fluorescence Resonance Energy Transfer Analysis on the Direct Interaction of Activation-2b with Histone H3/Switch-3B Protein in Arabidopsis Mesophyll Protoplasts - Lu Gao; Fangrui Lin; Danlu Han; Jieming Jiang; Chengwei Yang; Zhengfei Zhuang; Tongsheng Chen (Journal of Fluorescence, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Pressure Distribution and Deformation Control of Gob-Side Entry Retaining Formed by Roof Cutting Influenced by Abandoned Roadways - Xiaojie Yang; Lin Hou; Haojie Xue; Di Yuan; Jindong Cao; Zijie Han; Yubing Gao (Geotechnical and Geological Engineering, 2021)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

The Efficacy and Safety of Transcranial Direct Current Stimulation for Cerebellar Ataxia: a Systematic Review and Meta-Analysis - Tiffany X. Chen; Chen-Ya Yang; Gloria Willson; Chih-Chun Lin; Sheng-Han Kuo (The Cerebellum, 2021)

Paleoglacial and paleoclimate reconstructions during the global Last Glacial Maximum in the Longriba area, eastern Tibetan Plateau - Wei-lin Yang; Ye-song Han; Xu Peng; Ze-ze Ran; Qing Liu; Geng-nian Liu (Journal of Mountain Science, 2021)

Method for fast staining and obtaining high-magnification and high-resolution cell images of Nicotiana benthamiana - Yuanyuan Jiang; Jiangrong Peng; Yunpeng Cao; Zhiqiang Han; Ling Zhang; Wenbing Su; Shunquan Lin; Yuan Yuan; Bin Wang; Xianghui Yang; Zhike Zhang (Physiology and Molecular Biology of Plants, 2021)

Isolation and characterization of two new chroman-4-ones from the endophytic fungus Penicillium chrysogenum obtained from Eucommia ulmoides Oliver - Sheng-Yue Liu; Li-Zhi Wang; Yue-Fei Wang; Lin Li; Guo-Ying Han; Bing-Yang Zhang; Ying Guo; Yong-Zhi He; Shi-Ming Fang; Han Zhang (Natural Product Research, 2020)

Functional human brain connectivity during labor and its alteration under epidural analgesia - Fan-Pei Yang; An-Shine Chao; Sung-Han Lin; Anne Chao; Tzu-Hao Wang; Yao-Lung Chang; Hong-Shiu Chang; Jiun-Jie Wang (Brain Imaging and Behavior, 2020)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Evaluation on the allocative efficiency of agricultural factors in the five Central Asian countries - Guogang Wang; Lin Zhang; Yuzhu Sun; Yantao Yang; Chengji Han (Journal of Geographical Sciences, 2020)

Complete mitochondrial genome of the freshwater fish Acrossocheilus longipinnis (Teleostei: Cyprinidae): genome characterization and phylogenetic analysis - Xiao-Jing Hou; Hung-Du Lin; Wen-Qiao Tang; Dong Liu; Chiao-Chuan Han; Jin-Quan Yang (Biologia, 2020)

Complete genome sequence of a novel recombinant avian leukosis virus isolated from a three-yellow chicken - Tao Sun; Ximei Wang; Wei Han; Xiaoling Ma; Weili Yin; Baohai Fang; Xiao Lin; Yang Li (Archives of Virology, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

Zooplankton in a continuous waterscape: environmental and spatial factors shaping spring zooplankton community structure in a large canyon reservoir at the tropic of cancer - Eric Zeus C. Rizo; Ping Liu; Haiyu Niu; Yang Yang; Qiuqi Lin; Rey Donne S. Papa; Henri J. Dumont; Bo-Ping Han (Hydrobiologia, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Miscanthus cultivation shapes rhizosphere microbial community structure and function as assessed by Illumina MiSeq sequencing combined with PICRUSt and FUNGUIld analyses - Yan Chen; Wei Tian; Yang Shao; Ying-Jun Li; Li-An Lin; Ying-Jun Zhang; Hui Han; Zhao-Jin Chen (Archives of Microbiology, 2020)

Insights into facile synthesized pomelo biochar adsorbing thallium: potential remediation in agricultural soils - Chunbai Gao; Yinglan Cao; Jianqing Lin; Hongda Fang; Zhuanxi Luo; Yang Lin; Han Zhao; Yicheng Huang (Environmental Science and Pollution Research, 2020)

Baicalein attenuates caspase-independent cells death via inhibiting PARP-1 activation and AIF nuclear translocation in cerebral ischemia/reperfusion rats - Wei-Han Li; Ying-Lin Yang; Xiao Cheng; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Apoptosis, 2020)

Dynamic Alterations of Brain Injury, Functional Recovery, and Metabolites Profile after Cerebral Ischemia/Reperfusion in Rats Contributes to Potential Biomarkers - Xiao Cheng; Ying-Lin Yang; Wei-Han Li; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Journal of Molecular Neuroscience, 2020)

A chronosequence study of purple paddy soils with respect to improving ammonium and potassium fertilization management - Guang-Zhong Han; Lai-Ming Huang; Gan-Lin Zhang; Fan Yang (Journal of Soils and Sediments, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Endothelial Notch activation promotes neutrophil transmigration via downregulating endomucin to aggravate hepatic ischemia/reperfusion injury - Peiran Zhang; Kangyi Yue; Xinli Liu; Xianchun Yan; Ziyan Yang; Juanli Duan; Congcong Xia; Xinyuan Xu; Mei Zhang; Liang Liang; Lin Wang; Hua Han (Science China Life Sciences, 2020)

Anti- β -amyloid aggregation activity of enantiomeric furolactone-type lignans from Archidendron clypearia (Jack) I.C.N. - Yu-Xi Wang; Bin Lin; Le Zhou; Zhi-Yang Yan; Han Zhang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2020)

Characterization of a Saccharum spontaneum with a basic chromosome number of x = 10 provides new insights on genome evolution in genus Saccharum - Zhuang Meng; Jinlei Han; Yujing Lin; Yiyong Zhao; Qingfang Lin; Xiaokai Ma; Jianping Wang; Muqing Zhang; Liangsheng Zhang; Qinghui Yang; Kai Wang (Theoretical and Applied Genetics, 2020)

Bin-based genome-wide association analyses improve power and resolution in QTL mapping and identify favorable alleles from multiple parents in a four-way MAGIC rice population - Zhongmin Han; Gang Hu; Hua Liu; Famao Liang; Lin Yang; Hu Zhao; Qinghua Zhang; Zhixin Li; Qifa Zhang; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Overexpression of AtAGT1 promoted root growth and development during seedling establishment - Rui Wang; Lin Yang; Xiaofang Han; Yuhong Zhao; Ling Zhao; Beibei Xiang; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell Reports, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Effects of exogenous putrescine on the ultrastructure of and calcium ion flow rate in lettuce leaf epidermal cells under drought stress - Xu Zhu; Lin Wang; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

Spatial heterogeneity of spring phytoplankton in a large tropical reservoir: could mass effect homogenize the heterogeneity by species sorting? - Yang Yang; Haiyu Niu; Lijuan Xiao; Qiuqi Lin; Bo-Ping Han; Luigi Naselli-Flores (Hydrobiologia, 2018)

Association between prenatal nickel exposure and preterm low birth weight: possible effect of selenium - Xiaojie Sun; Yangqian Jiang; Wei Xia; Shuna Jin; Wenyu Liu; Xin Lin; Hongxiu Liu; Xiaomei Chen; Yang Peng; Han Li; Bin Lu; Shunqing Xu; et al. (Environmental Science and Pollution Research, 2018)

Phenolic acid production is more effectively enhanced than tanshinone production by methyl jasmonate in Salvia miltiorrhiza hairy roots - Bingcong Xing; Dongfeng Yang; Lin Liu; Ruilian Han; Yanfang Sun; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells - Zhihao Xu; Wenbin Nan; Xiaoyue Zhang; Yuliang Sun; Jichao Yang; Kecheng Lu; Yalin Liu; Yaoxin Gao; Fen Yang; Wenchao Mao; Xuekun Xing; Jiang Du; et al. (Journal of Molecular Neuroscience, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Species-based classification reveals spatial processes of phytoplankton meta-communities better than functional group approaches: a case study from three freshwater lake regions in China - Li-Juan Xiao; Yiqiu Zhu; Yang Yang; Qiuqi Lin; Bo-Ping Han; Judit Padisák (Hydrobiologia, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

Sonic Hedgehog Regulation of the Neural Precursor Cell Fate During Chicken Optic Tectum Development - Ciqing Yang; Xiaoying Li; Qiuling Li; Han Li; Liang Qiao; Zhikun Guo; Juntang Lin (Journal of Molecular Neuroscience, 2018)

Spa therapy (balneotherapy) relieves mental stress, sleep disorder, and general health problems in sub-healthy people - Bei Yang; Qi-zhong Qin; Ling-li Han; Jing Lin; Yu Chen (International Journal of Biometeorology, 2018)

Spatial structure and β-diversity of phytoplankton in Tibetan Plateau lakes: nestedness or replacement? - Yang Yang; Ren Hu; Qiuqi Lin; Juzhi Hou; Yongqin Liu; Bo-Ping Han; Luigi Naselli-Flores (Hydrobiologia, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Design, synthesis, antitumor evaluation, 3D-QSAR and molecular docking studies of novel 4-aminoacridone compounds - Lin Tian; Chang J. Feng; Tong X. Li; Zhao Li; Wei H. Yang; Xiang E. Han (Medicinal Chemistry Research, 2017)

Regulatory element-based prediction identifies new susceptibility regulatory variants for osteoporosis - Shi Yao; Yan Guo; Shan-Shan Dong; Ruo-Han Hao; Xiao-Feng Chen; Yi-Xiao Chen; Jia-Bin Chen; Qing Tian; Hong-Wen Deng; Tie-Lin Yang (Human Genetics, 2017)

The monitoring and analysis of the coastal lowland subsidence in the southern Hangzhou Bay with an advanced time-series InSAR method - Peng Han; Xiaoxia Yang; Lin Bai; Qishi Sun (Acta Oceanologica Sinica, 2017)

Naturally occurring furanoditerpenoids: distribution, chemistry and their pharmacological activities - Han Bao; Qingwen Zhang; Yang Ye; Ligen Lin (Phytochemistry Reviews, 2017)

Erratum to: Lentiviral-Mediated Netrin-1 Overexpression Improves Motor and Sensory Functions in SCT Rats Associated with SYP and GAP-43 Expressions - Xue Fei Han; Yuan Zhang; Liu Lin Xiong; Yang Xu; Piao Zhang; Qing Jie Xia; Ting Hua Wang; Ying Chun Ba (Molecular Neurobiology, 2017)

Apigenin alleviates STZ-induced diabetic cardiomyopathy - Huang-Jun Liu; Yun-Lin Fan; Hai-Han Liao; Yuan Liu; Si Chen; Zhen-Guo Ma; Ning Zhang; Zheng Yang; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

NH3-SCR Performance of Mn-Fe/TiO2 Catalysts at Low Temperature in the Absence and Presence of Water Vapor - Lin Zhu; Zhaoping Zhong; Han Yang; Chunhua Wang (Water, Air, & Soil Pollution, 2016)

Genome-Wide Discovery of Tissue-Specific Genes in Maize - Feng Lin; Huabin Bao; Jun Yang; Yuhe Liu; Huixue Dai; Han Zhao (Plant Molecular Biology Reporter, 2016)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

N-cadherin regulates beta-catenin signal and its misexpression perturbs commissural axon projection in the developing chicken spinal cord - Ciqing Yang; Xiaoying Li; Congrui Wang; Sulei Fu; Han Li; Zhikun Guo; Shanting Zhao; Juntang Lin (Journal of Molecular Histology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Impact of heat waves on nonaccidental deaths in Jinan, China, and associated risk factors - Jun Zhang; Shouqin Liu; Jing Han; Lin Zhou; Yueling Liu; Liu Yang; Ji Zhang; Ying Zhang (International Journal of Biometeorology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Gene characterization and transcription analysis of two new ammonium transporters in pear rootstock (Pyrus betulaefolia) - Hui Li; Jin-Long Han; You-Hong Chang; Jing Lin; Qing-Song Yang (Journal of Plant Research, 2016)

Optimization Studies on Prokaryotic Cell Expression of the Human Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL) - Lin Hao; Zhi-Guo Zhang; Zheng-Duo Shi; Kun Pang; Jun-Jie Zhang; Yang Dong; Cong-Hui Han (Cell Biochemistry and Biophysics, 2015)

A γ-Glutamylcysteine Synthetase Gene from Pyrus calleryana Is Responsive to Ions and Osmotic Stresses - Hui Li; Jin-long Han; Jing Lin; Qing-song Yang; You-hong Chang (Plant Molecular Biology Reporter, 2015)

Immunological markers predict the prognosis of patients with squamous non-small cell lung cancer - Long Jiang; Zerui Zhao; Shanshan Jiang; Yongbin Lin; Han Yang; Zehua Xie; Yaobin Lin; Hao Long (Immunologic Research, 2015)

Association analyses of FGFR2 gene polymorphisms with femoral neck bone mineral density in Chinese Han population - Shan-Shan Dong; Tie-Lin Yang; Han Yan; Zheng-Qin Rong; Jia-Bin Chen; Ruo-Han Hao; Xiao-Feng Chen; Yan Guo (Molecular Genetics and Genomics, 2015)

Pedogenetic evolution of clay minerals and agricultural implications in three paddy soil chronosequences of south China derived from different parent materials - Guang-Zhong Han; Gan-Lin Zhang; De-Cheng Li; Jin-Ling Yang (Journal of Soils and Sediments, 2015)

The inner opercular membrane of the euryhaline teleost: a useful surrogate model for comparisons of different characteristics of ionocytes between seawater- and freshwater-acclimated medaka - Chao-Kai Kang; Shu-Yuan Yang; Shang-Tao Lin; Tsung-Han Lee (Histochemistry and Cell Biology, 2015)

Halorussus ruber sp. nov., isolated from an inland salt lake of China - Wei-Dong Xu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Kun Yang (Archives of Microbiology, 2015)

Indoor/outdoor pollution level and personal inhalation exposure of polycyclic aromatic hydrocarbons through biomass fuelled cooking - Guofeng Shen; Yanyan Zhang; Siye Wei; Yuanchen Chen; Chunli Yang; Pengchuan Lin; Han Xie; Miao Xue; Xilong Wang; Shu Tao (Air Quality, Atmosphere & Health, 2014)

Evaluation of Flow Velocity in Unilateral Middle Cerebral Artery Stenosis by Transcranial Doppler - Lin Wang; Yingqi Xing; Yang Li; Ke Han; Jiafeng Chen (Cell Biochemistry and Biophysics, 2014)

Contamination and distribution of parent, nitrated, and oxygenated polycyclic aromatic hydrocarbons in smoked meat - Yuanchen Chen; Guofeng Shen; Shu Su; Huizhong Shen; Ye Huang; Tongchao Li; Wei Li; Yanyan Zhang; Yan Lu; Han Chen; Chunli Yang; Nan Lin; et al. (Environmental Science and Pollution Research, 2014)

The study of regulatory effects of Pdx-1, MafA and NeuroD1 on the activity of porcine insulin promoter and the expression of human islet amyloid polypeptide - Xiao-Dan Liu; Jin-Xue Ruan; Ji-Han Xia; Shu-Lin Yang; Jun-Hua Fan; Kui Li (Molecular and Cellular Biochemistry, 2014)

Antidepressant-like effects of the phosphodiesterase-4 inhibitor etazolate and phosphodiesterase-5 inhibitor sildenafil via cyclic AMP or cyclic GMP signaling in mice - Chuang Wang; Jianrui Zhang; Yang Lu; Peipei Lin; Tonghe Pan; Xin Zhao; Aiming Liu; Qinwen Wang; Wenhua Zhou; Han-Ting Zhang (Metabolic Brain Disease, 2014)

Human hepatocellular carcinoma-infiltrating CD4+CD69+Foxp3− regulatory T cell suppresses T cell response via membrane-bound TGF-β1 - Yanmei Han; Yuan Yang; Zhubo Chen; Zhengping Jiang; Yan Gu; Yanfang Liu; Sheng Xu; Chuan Lin; Zeya Pan; Weiping Zhou; Xuetao Cao (Journal of Molecular Medicine, 2014)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Overexpression of the Arabidopsis photorespiratory pathway gene, serine: glyoxylate aminotransferase (AtAGT1), leads to salt stress tolerance in transgenic duckweed (Lemna minor) - Lin Yang; Huajun Han; Miaomiao Liu; Zhaojiang Zuo; Kaiqiang Zhou; Jianchao Lü; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Isolation and characterization of a long-chain acyl-coenzyme A synthetase encoding gene from the marine microalga Nannochloropsis oculata - Lin Zhang; Xiaolei Ma; Guanpin Yang; Baohua Zhu; Jichang Han; Wengong Yu; Kehou Pan (Journal of Applied Phycology, 2012)

Pharmacokinetics, Tissue Distribution, and Plasma Protein Binding Study of Platinum Originating from Dicycloplatin, a Novel Antitumor Supramolecule, in Rats and Dogs by ICP-MS - Di Zhao; Yongjie Zhang; Chunxiang Xu; Can Dong; Hui Lin; Lingli Zhang; Cuiyun Li; Shuangxia Ren; Xin Wang; Shuoye Yang; Deen Han; Xijing Chen (Biological Trace Element Research, 2012)

Effect of particle size of titanium dioxide nanoparticle aggregates on the degradation of one azo dye - Yang-hsin Shih; Cheng-han Lin (Environmental Science and Pollution Research, 2012)

TFF3 mediated induction of VEGF via hypoxia in human gastric cancer SGC-7901 cells - Bayasi Guleng; Jia Han; Jin-Qiu Yang; Qing-Wen Huang; Jian-Kun Huang; Xiao-Ning Yang; Jing-Jing Liu; Jian-Lin Ren (Molecular Biology Reports, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Mechanism of Monoclonal Antibody-Coupled Staphylococcus Superantigen-A Induced Apoptosis in Human Bladder Cancer Cells - Conghui Han; Zhen Gong; Lin Hao; Jianjun Yang; Jianpeng Hu; Bingzheng Dong; Tao Fan; Wenhao Tang; Gaojun Teng (Cell Biochemistry and Biophysics, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Effects of C-terminal amino acids truncation on enzyme properties of Aeromonas caviae D1 chitinase - Fu-Pang Lin; Hsu-Han Chuang; Yi-Hsuan Liu; Chia-Yu Hsieh; Pei-Wen Lin; Hsu-Yang Lin (Archives of Microbiology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

A new species of Rhinogobius (Teleostei: Gobiidae) from the Feiyunjiang Basin in Zhejiang Province, China - Jin-Quan Yang; Han-Lin Wu; I-Shiung Chen (Ichthyological Research, 2008)

Biochemical characterization of engineered amylopullulanase from Thermoanaerobacter ethanolicus 39E-implicating the non-necessity of its 100 C-terminal amino acid residues - Hsu-Yang Lin; Hsu-Han Chuang; Fu-Pang Lin (Extremophiles, 2008)

Effect of drought and low light on growth and enzymatic antioxidant system of Picea asperata seedlings - Yan Yang; Chao Han; Qing Liu; Bo Lin; Jianwen Wang (Acta Physiologiae Plantarum, 2008)

A RAV-like transcription factor controls photosynthesis and senescence in soybean - Lin Zhao; Qiulan Luo; Chunliang Yang; Yingpeng Han; Wenbin Li (Planta, 2008)

Xylitol conversion by fermentation using five yeast strains and polyelectrolyte-assisted ultrafiltration - Chun-Han Ko; Pei-Chun Chiu; Chin-Lin Yang; Keng-Hao Chang (Biotechnology Letters, 2007)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular Cloning and Expression Analysis of the Myostatin Gene in Sea Perch (Lateolabrax japonicus) - Han-Qing Ye; Song-Lin Chen; Zhen-Xia Sha; Yang Liu (Marine Biotechnology, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.

A Novel Alginate Lyase with High Activity on Acetylated Alginate of Pseudomonas aeruginosa FRD1 from Pseudomonas sp. QD03 - Lin Xiao; Feng Han; Zhao Yang; Xin-zhi Lu; Wen-gong Yu (World Journal of Microbiology and Biotechnology, 2006)

Effects of Cycle Time on Properties of Aerobic Granules in Sequencing Batch Airlift Reactors - Fang Wang; Feng-lin Yang; Xing-wen Zhang; Yi-hui Liu; Han-min Zhang; Jun Zhou (World Journal of Microbiology and Biotechnology, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)